Cover member for foldable flexible display, base film for cover member for foldable flexible display, and display device including same
By using base films and transparent substrates of specific thicknesses and materials in the cover film, the problem that the cover film is not easy to fold when repeatedly bending is solved, and convenient processing and protection functions are achieved.
Patent Information
- Application Number
- JP2023113377
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-09-17
- Filing Date
- 2023-07-11
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2041-08-30
AI Technical Summary
The prior art is difficult to prevent the cover film from folding with the base film when repeatedly bending without damaging the protective function.
By using a base film and a transparent substrate of a specific thickness in the cover film, and controlling the material composition and density relationship of the base film, it is not easy to fold when bending.
The covering film does not fold with the base film when repeatedly bending, improves the convenience of processing and maintains the protection function.
Smart Images

Figure 0007670089000009 
Figure 0007670089000010 
Figure 0007670089000011
Abstract
Description
[Technical field]
[0001] The present invention relates to Foldable flexible displays Cover member, Foldable flexible displays The present invention relates to a base film for a cover member and a display device including the same. More specifically, the present invention relates to a cover member that improves the handleability of the cover member and does not leave fold marks on the base film provided on the cover member, a base film for the cover member, and a display device including the same. [Background technology]
[0002] Recently, there has been much development of foldable or rollable flexible displays. Such displays are composed of a display unit having a cover glass unit (hereinafter, also referred to as a "cover member" in the present invention) for protecting the display and a polarizing plate.
[0003] Here, when using a glass substrate as the transparent substrate for the cover glass unit, flexibility is required, and therefore the glass substrate itself needs to be thin. In response to this demand, a method for manufacturing thin glass has been disclosed (see, for example, Patent Document 1).
[0004] Meanwhile, an invention has been disclosed that controls waviness on the surface of a polymer layer when the polymer layer (protective film) is laminated on a glass substrate for the purpose of protecting the glass substrate (see, for example, Patent Document 2).
[0005] In the flexible display having the folding specification, the bending radius of the cover member tends to become smaller when the display is folded by making each member thinner. In this case, according to the study by the present inventors, it was found that the protective film (also called "substrate film" in the present invention) provided on the cover member is required to have an improved protective function (push strength) to such an extent that the glass substrate does not crack when the cover member is folded, and also to have a property that does not leave a fold mark on the protective film when the cover member is repeatedly bent.
[0006] However, in a cover member constructed as a laminate of a glass substrate and a protective film prepared by the technical means disclosed above, it was difficult to achieve both an improvement in the protective function when made thinner and the property of preventing the protective film from leaving creases when repeatedly bent. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2017 / 066924 [Patent Document 2] Special Publication No. 2002-534305 Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention has been made in consideration of the above problems and circumstances, and the problem to be solved is as follows: Foldable flexible displays The object of the present invention is to provide a cover member which improves the handleability of the cover member and which does not leave creases in the base film provided on the cover member when repeatedly bent, a base film for the cover member, and a display device provided with them. [Means for solving the problem]
[0009] In the course of investigating the causes of the above problems in order to solve the above-mentioned problems, the present inventors discovered that when a cover member has a base film having a specific thickness and a transparent base material, and a specific relationship is satisfied between the stress of the base film and the strain thereon, a cover member can be obtained which not only has improved handleability but also has the property of not leaving fold marks on the base film provided in the cover member.
[0010] That is, the above-mentioned problems of the present invention are solved by the following means.
[0011] 1. base Material film and transparent base Materials Have Foldable flexible displays A cover member, The thickness of the base film is within the range of 1 μm or more and less than 15 μm, The thickness of the transparent substrate is in the range of 5 μm or more and less than 50 μm, the base film contains a cellulose ester resin, a cycloolefin resin, a fumaric acid diester resin, a polypropylene resin, a (meth)acrylic resin, a polyester resin, a polyarylate resin, a polyimide resin, a styrene resin, or a composite resin thereof; The base film The relationship between tensile stress and tensile elongation at break was measured under conditions of 23℃, 55% RH, and a tensile speed of 50 mm / min. The vertical axis represents stress (MPa) and the horizontal axis represents tensile elongation at break (%). The slope of the line connecting the origin and the breaking point on the stress-strain curve is 、 1.1 MPa / % Over 25.0 MPa / % below Within the range is Characterized by Foldable flexible displays Cover member.
[0012] 2. When the surface of the base film that is attached to the transparent base material is surface A and the back surface of the base film opposite surface A is surface B, The film density (ρ A ) is the film density (ρ B ) according to claim 1. Foldable flexible displays Cover member.
[0013] 3. When the surface of the base film that is attached to the transparent base material is surface A and the back surface of the base film opposite surface A is surface B, The film density (ρ A ) versus the film density (ρ B ) ratio (ρ A / ρ B 3. The method according to claim 1, wherein the value of is within a range of 0.80 to 0.95. Foldable flexible displays Cover member.
[0014] 4. The base film contains rubber particles in the range of 40 to 85% by mass. or Second In the section Described Foldable flexible displays Cover member.
[0015] 5. The transparent substrate has an elastic modulus of 55 to 80 GPa, and the ratio of the elastic modulus of the transparent substrate to the elastic modulus of the substrate film (elastic modulus of transparent substrate / elastic modulus of substrate film) is 30 or more. or No. In item 2 Described Foldable flexible displays Cover member. 6. A cover member for a foldable flexible display according to item 1 or 2, wherein the base film contains at least a polyimide resin. 7. A cover member for a foldable flexible display described in item 1 or 2, characterized in that the base film does not contain rubber particles.
[0016] 8. The thickness of the base film is within the range of 1 μm or more and less than 15 μm, the base film contains a cellulose ester resin, a cycloolefin resin, a fumaric acid diester resin, a polypropylene resin, a (meth)acrylic resin, a polyester resin, a polyarylate resin, a polyimide resin, a styrene resin, or a composite resin thereof; The base film The relationship between tensile stress and tensile elongation at break was measured under conditions of 23℃, 55% RH, and a tensile speed of 50 mm / min. The vertical axis represents stress (MPa) and the horizontal axis represents tensile elongation at break (%). The slope of the line connecting the origin and the breaking point on the stress-strain curve is 、 1.1 MPa / % Over 25.0 MPa / % below Within the range is Characterized by Foldable flexible displays Base film for cover members.
[0017] 9 The substrate film is attached to a transparent substrate, When the surface of the base film that is attached to the transparent base material is surface A and the back surface of the base film opposite surface A is surface B, The film density (ρ A ) is the film density (ρ B ) is smaller than the 8 The section Foldable flexible displays Base film for cover members.
[0018] 10 The substrate film is attached to a transparent substrate, When the surface of the base film that is attached to the transparent base material is surface A and the back surface of the base film opposite surface A is surface B, The film density (ρ A ) versus the film density (ρ B ) ratio (ρ A / ρ B ) is in the range of 0.80 to 0.95. 8 Section or Article 9 The section Foldable flexible displays Base film for cover members.
[0019] 11 The base film contains rubber particles in the range of 40 to 85% by mass. 8 term or No. In paragraph 9 Described Foldable flexible displays Base film for cover members.
[0020] 12 .Section 1 or No. In item 2 Described Foldable flexible displays Cover member or 8 term or No. In paragraph 9 Described Foldable flexible displays A display device comprising a base film for a cover member. Effect of the Invention
[0021] The above-mentioned means of the present invention can provide a cover member which not only improves the handleability of the cover member, but also prevents creases in the base film provided on the cover member when repeatedly bent, a base film for the cover member, and a display device provided with them.
[0022] Although the mechanism by which the effects of the present invention are expressed or the mechanism of action has not been clarified, it is speculated as follows.
[0023] The cover member of the present invention comprises a laminate of a substrate film having a specific thickness range and a transparent substrate, and is characterized in that the slope of the line connecting the origin and the breaking point on the stress-strain curve of the substrate film is 1.1 or more and 25.0 or less.
[0024] Due to such a feature, in addition to improving the handleability of the cover member, it is possible to obtain a cover member in which the base film provided on the cover member does not leave fold marks when the cover member is repeatedly bent.
[0025] Here, in the present invention, "handleability of the cover member" refers to the fact that the base film provided on the cover member exerts a protective function (push strength) during opening and closing by folding the cover member, and does not cause cracks, etc. in the transparent base material. Also, "fold marks" refers to the fact that, with repeated opening and closing by folding, the base film whitens at the folding site, which is observed as a fold line, and in addition, the base film peels off from the transparent base material, causing deterioration in visibility such as image distortion.
[0026] When the slope of the line connecting the origin and the breaking point in the stress-strain curve of the base film exceeds 25.0, that is, when the base film is stiff and reaches the breaking point quickly, a sudden increase in stress occurs especially on the outside of the base film when the base film is stretched, i.e., when the device is closed, and thus a difference in physical property deterioration occurs between the outside and inside during repeated opening and closing operations, causing whitening of the folded part or poor adhesion, which is visually recognized as the "fold marks". Furthermore, it is presumed that the transparent substrate is easily cracked because stress is directly concentrated on the transparent substrate when the transparent substrate is pressed.
[0027] On the other hand, when the slope of the straight line is less than 1.1 and the base film is soft, the difference in physical property deterioration between the outside and inside is unlikely to occur during repeated opening and closing operations, but the base film as a whole repeats expansion and contraction in a manner that the base film follows the transparent substrate integrally with the opening and closing operations, so that the base film floats up due to poor adhesion at the folded portion, reducing visibility. Furthermore, it is presumed that when the base film is pressed in together with the transparent substrate, the base film is too soft, so that the amount of physical deformation of the transparent substrate becomes too large, and the transparent substrate is likely to crack. [Brief description of the drawings]
[0028] [Figure 1A] Cross-sectional view of a laminate of a base film and a transparent base [Figure 1B] 1 is a cross-sectional view of another embodiment of a laminate of a substrate film and a transparent substrate. [Figure 1C] Schematic diagram of the laminate folded [Figure 1D] Schematic diagram of another embodiment of a laminate folded. [Diagram 2] A graph showing the stress-strain curve of the base film and the slope of the line connecting the origin and the breaking point [Diagram 3] FIG. 1 is a schematic diagram showing a method for producing a base film according to an embodiment of the present invention. [Figure 4] FIG. 1 is a schematic diagram showing an example of a method for producing a glass substrate used in a transparent substrate; [Figure 5A] Schematic diagram showing lamination of a substrate film with a support and a transparent substrate [Figure 5B] FIG. 1 is a schematic diagram showing lamination of a substrate film with a support and a transparent substrate according to another embodiment. [Figure 6] An example of application of a cover member to an organic EL display, which is an example of the display device of the present invention DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] The present invention Foldable flexible displays The cover member is , base Material Fill Mu and Toru Akimoto Materials Have Foldable flexible displays A cover member, the thickness of the base film is within the range of 1 μm or more and less than 15 μm, the thickness of the transparent base material is within the range of 5 μm or more and less than 50 μm, and the base film contains a cellulose ester resin, a cycloolefin resin, a fumaric acid diester resin, a polypropylene resin, a (meth)acrylic resin, a polyester resin, a polyarylate resin, a polyimide resin, a styrene resin, or a composite resin thereof; The base film The relationship between tensile stress and tensile elongation at break was measured under conditions of 23℃, 55% RH, and a tensile speed of 50 mm / min. The vertical axis represents stress (MPa) and the horizontal axis represents tensile elongation at break (%). The slope of the line connecting the origin and the breaking point on the stress-strain curve is 、 1.1 MPa / % Over 25.0 MPa / % below Within the range This feature is a technical feature common to or corresponding to the following embodiments.
[0030] As an embodiment of the present invention, from the viewpoint of exerting the effects of the present invention, when the surface of the base film that is attached to the transparent base material is surface A and the back surface of the base film opposite to surface A is surface B, the film density of surface A (ρ A ) is the film density (ρ B ) is preferably smaller than the film density (ρ A ) versus the film density (ρ B ) ratio (ρ A / ρ B ) is preferably within a range of 0.80 to 0.95. This is because, when the cover member is folded onto the transparent substrate side, a greater tensile stress is applied to the B-side of the substrate film than to the A-side, but if the film density on the A-side is low, the tensile stress can be alleviated.
[0031] The base film preferably contains rubber particles in the range of 40 to 85% by mass, which improves impact resistance due to the addition of a large amount of rubber particles, leading to improved resistance to fold marks when repeatedly bent.
[0032] It is preferable that the elastic modulus of the transparent substrate is within a range of 55 to 80 GPa, and the elastic modulus ratio of the elastic modulus of the transparent substrate to the base film (elastic modulus of transparent substrate / elastic modulus of base film) is at least 30. This is because, in order to provide a cover member having improved indentation strength and free of folding marks by using a transparent substrate having a low elastic modulus due to thinning, it is necessary to use a base film with a lower elastic modulus, that is, by setting the elastic modulus ratio (elastic modulus of transparent substrate / elastic modulus of base film) to the transparent substrate at 30 or more, the protective function of the transparent substrate can be further improved.
[0033] In addition, the present invention Foldable flexible displays The thickness (also called "film thickness") of the base film for the cover member is in the range of 1 μm or more and less than 15 μm. the substrate film contains a cellulose ester resin, a cycloolefin resin, a fumaric acid diester resin, a polypropylene resin, a (meth)acrylic resin, a polyester resin, a polyarylate resin, a polyimide resin, a styrene resin, or a composite resin thereof; The base film The relationship between tensile stress and tensile elongation at break was measured under conditions of 23℃, 55% RH, and a tensile speed of 50 mm / min. The vertical axis represents stress (MPa) and the horizontal axis represents tensile elongation at break (%). The slope of the line connecting the origin and the breaking point on the stress-strain curve is 、 1.1 MPa / % Over 25.0 MPa / % By adjusting the inclination of the straight line within the above range, the pressing strength and fold mark resistance of the base film are improved, and the handleability of the base film when provided in a cover member is improved.
[0034] When the surface of the base film that is attached to the transparent base material is designated as surface A and the back surface of the base film opposite surface A is designated as surface B, the film density of surface A (ρ A ) is the film density (ρ B ) is preferably smaller than the film density (ρ A ) versus the film density (ρ B ) ratio (ρ A / ρ B From the viewpoint of the above-mentioned effects, it is more preferable that the value of is within the range of 0.80 to 0.95.
[0035] Similarly, it is preferable that the base film contains rubber particles in the range of 40 to 85% by mass.
[0036] The display device of the present invention is characterized by comprising the cover member of the present invention or the base film for the cover member of the present invention. This display device not only improves the handleability of the cover member, but also makes it possible to obtain a display device having a foldable display or a rollable display in which the base film provided on the cover member does not leave creases when repeatedly bent.
[0037] The present invention, its components, and embodiments for carrying out the present invention will be described in detail below. In this application, the symbol "to" is used to mean that the numerical values before and after the symbol "to" are included as the lower and upper limits.
[0038] <Overview of the cover member of the present invention> The present invention Foldable flexible displays The cover member is , base Material Fill Mu and Toru Akimoto Materials Have Foldable flexible displays A cover member, the thickness of the base film is within the range of 1 μm or more and less than 15 μm, the thickness of the transparent base material is within the range of 5 μm or more and less than 50 μm, and the base film contains a cellulose ester resin, a cycloolefin resin, a fumaric acid diester resin, a polypropylene resin, a (meth)acrylic resin, a polyester resin, a polyarylate resin, a polyimide resin, a styrene resin, or a composite resin thereof; The base film The relationship between tensile stress and tensile elongation at break was measured under conditions of 23℃, 55% RH, and a tensile speed of 50 mm / min. The vertical axis represents stress (MPa) and the horizontal axis represents tensile elongation at break (%). The slope of the line connecting the origin and the breaking point on the stress-strain curve is 、 1.1 MPa / % Over 25.0 MPa / % below Within the range It is characterized in that:
[0039] FIG. 1 is a cross-sectional view of a laminate of a base film and a transparent base material in a cover member of the present invention, and a schematic diagram of the cover member (laminate) when folded.
[0040] 1A shows the minimum configuration of a cover member 10 of the present invention, in which a laminate is formed by bonding a base film 1 to a transparent base material 3 via a pressure-sensitive adhesive layer 4. When the base film 1 is bonded to the transparent base material 3, the surface of the base film 1 that is bonded to the transparent base material 3 is designated as side A, and the back side of the base film opposite side A is designated as side B.
[0041] 1B shows another embodiment of the cover member 10 of the present invention. The embodiment shows a substrate film 1 attached to a transparent substrate 3 via an adhesive layer 4, and a substrate film 2 attached to the transparent substrate 3 via an adhesive layer 4 to form a laminate. The substrate film 2 may be a film having the same specifications as the substrate film 1, or may be a film made of a different material and having different specifications. For example, it may be a functional film such as a hard coat film in order to improve the surface hardness.
[0042] Fig. 1C is a schematic diagram of the cover member 10 shown in Fig. 1A folded towards the transparent substrate 3. Here, the bending radius when folded means the inner radius R of the folded portion when the cover member 10 is folded in Fig. 1C or 1D.
[0043] As mentioned above, when the cover member is folded toward the transparent substrate 3, more tensile stress is applied to the side B of the substrate film than to the side A. However, if the film density on the side A is low, this tensile stress can be alleviated.
[0044] Fig. 1D is a schematic diagram of the cover member 10 shown in Fig. 1B folded towards the transparent substrate 3. Even in this case, the surface B side of the substrate film 1 is subjected to a greater tensile stress than the surface A side, but if the film density on the surface A side is low, the tensile stress can be alleviated.
[0045] The stress-strain curve according to the present invention shows the relationship between the tensile stress and the tensile elongation at break of the base film, measured in accordance with JIS K7127:1999.
[0046] The substrate film is cut into a size of 100 mm (MD direction: lengthwise direction) x 10 mm (TD direction: widthwise direction) to obtain a sample film. This sample film is conditioned for 24 hours in an environment of 23°C and 55% RH, and the conditioned sample film is then pulled in the MD direction with an Orientec Tensilon RTC-1225A chuck at a distance of 50 mm in accordance with JIS K7127:1999 to obtain a stress-strain curve until breakage. The stress-strain curve is expressed as stress (MPa) on the vertical axis and tensile elongation at break (%) on the horizontal axis. The stress-strain curve is measured at 23°C and 55% RH at a pulling speed of 50 mm / min.
[0047] The method for determining the slope of the straight line according to the present invention from the stress-strain curve of the base film obtained by the above measurement will be explained with reference to the drawings.
[0048] FIG. 2 is a graph showing the stress-strain curve of a base film and the slope of the line connecting the origin and the breaking point.
[0049] When the base film is subjected to a tensile test, it is elongated to a breaking point X, and when a straight line Y is drawn connecting the breaking point X and the origin (0 point), the slope α of this line is defined in the present invention as "the slope of the line connecting the origin and the breaking point in the stress-strain curve of the base film". As described above, in order to obtain the effects of the present invention, the slope α needs to be 1.1 or more and 25.0 or less, and by being elastic but not too hard, it is possible to obtain a cover member that not only improves the handling of the cover member by improving the pressing strength of the base film, but also leaves no crease marks on the base film itself provided on the cover member when repeatedly bent.
[0050] The components of the present invention will be described in detail below. However, the present invention is not limited to these components in the following description.
[0051] [1] Base film [1.1] Overview of base film In the following description, the "base film" will be described as the "base film 1" in FIG. 1 unless otherwise specified.
[0052] The base film according to the present invention is characterized in that its thickness is within the range of 1 μm or more and less than 15 μm, and the slope of the line connecting the origin and the breaking point in the stress-strain curve of the base film is 1.1 or more and 25.0 or less. When used in a cover member, the base film not only improves the handling properties such as the pressing strength, but also has the effect of preventing fold marks from being left on the base film itself when it is repeatedly bent.
[0053] As described above, when the slope of the straight line exceeds 25.0, a sudden increase in stress occurs especially on the outside of the base film when the base film is stretched, i.e., when the device is closed, and thus a difference in physical property deterioration occurs between the outside and inside during repeated opening and closing operations, causing whitening of the folded portion or poor adhesion, which are visible as fold marks. Furthermore, when the transparent substrate is pressed in, stress is directly concentrated on the transparent substrate, which makes the transparent substrate prone to cracking.
[0054] On the other hand, if the slope of the straight line is less than 1.1 and the base film is soft, the base film will repeatedly expand and contract as a whole in a manner that the base film follows the transparent base material integrally with the opening and closing operation, and the base film will rise due to poor adhesion at the folded portion, reducing visibility and being visible as fold marks. Furthermore, when the base film is pressed in together with the transparent base material, the base film is too soft, so the amount of physical deformation of the transparent base material becomes too large, and the transparent base material is likely to crack.
[0055] If the film thickness is less than 1 μm, the stiffness of the base film is weak and the pressing strength of the cover member is reduced, whereas if the film thickness is 15 μm or more, the stiffness of the base film is strong and the fold marks are likely to be generated with repeated opening and closing of the display, so it is necessary to keep the film thickness within the above range.
[0056] Furthermore, when the surface of the base film that is attached to the transparent base material is designated as surface A and the back surface of the base film opposite to surface A is designated as surface B, the film density of surface A (ρ A ) is the film density (ρ B ) is preferably smaller than the film density (ρ A ) versus the film density (ρ B ) ratio (ρ A / ρ B ) is preferably within a range of 0.80 to 0.95. This is because, when the cover member is folded onto the transparent substrate side, a greater tensile stress is applied to the B-side of the substrate film than to the A-side, but if the film density on the A-side is low, the tensile stress can be alleviated.
[0057] <Measurement of density of sides A and B of base film> The density of the surface (side A and side B) of the base film is measured using X-ray reflectivity (XRR). When X-rays are incident on the film surface at a very shallow angle, they are totally reflected, and when the angle of the incident X-rays is equal to or greater than the critical angle of total reflection, the X-rays penetrate into the film and the reflectivity decreases. The reflectivity profile measured by the XRR method can be analyzed using dedicated reflectivity analysis software. In the present invention, when the angle at which the reflectivity starts to decrease is θa, the density at which the fitting error between the measurement result and the calculation result is the smallest in the range of 2θ from 2θa to 2θa+0.1° is defined as the surface density. At this time, the fitting is performed with the surface roughness in the range of 0 nm to 1 nm.
[0058] The substrate film is cut into a piece measuring 30 mm x 30 mm, fixed to a sample stage, and measured under the following measurement conditions. (Measurement conditions) Equipment: Thin film X-ray diffraction equipment (Rigaku ATX-G) Sample size: 30mm x 30mm ·Incoming X-ray wavelength: 1.5405Å Measurement range (θ): 0~6° Analysis software: Reflectance analysis software GXRR (Rigaku Corporation)
[0059] The film density (ρ A ) versus the film density (ρ B ) ratio (ρ A / ρ B In order to make the value of (a) fall within the range of 0.80 to 0.95, the following findings can be utilized, for example, in the manufacturing process of the base film.
[0060] (a) Changing the amount of rubber particles or fine particles relative to the resin. For example, increasing the amount of rubber particles or fine particles promotes the diffusion of the solvent, making it harder for density differences to occur between the front and back surfaces.
[0061] (b) Changing the solid content in the dope. For example, if the solid content is high, the amount of solvent is relatively small, so that density difference is less likely to occur.
[0062] (c) Change the drying method. For example, by adding spot drying (applying a heater to the surface) in addition to slow drying, the density difference can be increased.
[0063] By combining the methods derived from the knowledge of (a) to (c), the density ratio of the A surface to the B surface (ρ A / ρ B ) can be adjusted to within the range of 0.80 to 0.95.
[0064] [1.2] Material of the base film The resin used in the base film according to the present invention is not particularly limited, and examples thereof include cellulose ester resins, cycloolefin resins, fumaric acid diester resins, polypropylene resins, (meth)acrylic resins, polyester resins, polyarylate resins, polyimide resins, and styrene resins or composite resins thereof. Preferred resins include (meth)acrylic resins, styrene-(meth)acrylate copolymers, cycloolefin resins, and polyimide resins, which contain a linear polymer material having a carbonyl group in the side chain, or a polymer material having a cyclic structure in the main chain, from the viewpoints of controlling physical properties such as bending resistance and improving optical properties.
[0065] <(Meth)acrylic resin> The (meth)acrylic resin used in the base film preferably contains at least a structural unit (U1) derived from methyl methacrylate and a structural unit (U2) derived from phenylmaleimide. The (meth)acrylic resin containing the structural unit (U2) derived from phenylmaleimide has the advantage of reducing the photoelastic coefficient of the base film and preventing unevenness even when it absorbs moisture and expands.
[0066] The (meth)acrylic resin may further contain other structural units than those mentioned above. Examples of such other structural units include (meth)acrylic acid alkyl esters such as adamantyl acrylate; (meth)acrylic acid cycloalkyl esters such as 2-ethylhexyl acrylate. Among them, it is preferable to further contain a structural unit (U3) derived from an acrylic acid alkyl ester from the viewpoint of reducing the deterioration of brittleness caused by the inclusion of the structural unit (U2) derived from phenylmaleimide.
[0067] That is, the (meth)acrylic resin more preferably contains a structural unit (U1) derived from methyl methacrylate, a structural unit (U2) derived from phenylmaleimide, and a structural unit (U3) derived from an alkyl acrylate.
[0068] The content of the structural unit (U1) derived from methyl methacrylate is preferably in the range of 50 to 95 mass %, and more preferably in the range of 70 to 90 mass %, based on all structural units constituting the (meth)acrylic resin.
[0069] The structural unit (U2) derived from phenylmaleimide has a relatively rigid structure, which can improve the mechanical strength of the base film. In addition, the structural unit (U2) derived from phenylmaleimide has a relatively bulky structure, which can have microvoids that can move rubber particles in the resin matrix, which can make the rubber particles more likely to be unevenly distributed in the surface layer of the base film.
[0070] The content of the structural unit (U2) derived from phenylmaleimide is preferably in the range of 1 to 25% by mass based on all structural units constituting the (meth)acrylic resin. When the content of the structural unit (U2) derived from phenylmaleimide is 1% by mass or more, the base film has excellent storage stability in a high humidity environment. When it is 25% by mass or less, the brittleness of the base film is unlikely to be excessively impaired. From the above viewpoints, the content of the structural unit (U2) derived from phenylmaleimide is more preferably in the range of 7 to 15% by mass.
[0071] The structural unit (U3) derived from an alkyl acrylate can impart appropriate flexibility to the resin, and can therefore improve the brittleness caused by including, for example, the structural unit (U2) derived from a phenylmaleimide.
[0072] The alkyl acrylate is preferably an alkyl acrylate having an alkyl moiety with 1 to 7 carbon atoms, preferably 1 to 5. Examples of the alkyl acrylate include methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, 2-hydroxyethyl acrylate, hexyl acrylate, and 2-ethylhexyl acrylate.
[0073] The content of the structural unit (U3) derived from an acrylic acid alkyl ester is preferably in the range of 1 to 25% by mass based on the total structural units constituting the (meth)acrylic resin. When the content of the structural unit (U3) derived from an acrylic acid alkyl ester is 1% by mass or more, the (meth)acrylic resin can be given an appropriate flexibility, so that the base film does not become too brittle and is difficult to break. When the content of the structural unit (U3) derived from an acrylic acid alkyl ester is 25% by mass or less, the Tg of the base film does not become too low, and the base film has excellent storage stability in a high humidity environment. From the above viewpoint, the content of the structural unit (U3) derived from an acrylic acid alkyl ester is more preferably in the range of 5 to 15% by mass.
[0074] The ratio of the structural unit (U2) derived from phenylmaleimide to the total amount of the structural unit (U2) derived from phenylmaleimide and the structural unit (U3) derived from an alkyl acrylate is preferably in the range of 20 to 70% by mass. When the ratio is 20% by mass or more, the elastic modulus of the base film is easily increased, and when it is 70% by mass or less, the base film does not become too brittle.
[0075] The glass transition temperature (Tg) of the (meth)acrylic resin is preferably 100° C. or higher, and more preferably in the range of 120 to 150° C. When the Tg of the (meth)acrylic resin is within the above range, the heat resistance of the base film is easily improved. In order to adjust the Tg of the (meth)acrylic resin, it is preferable to adjust the content of, for example, the structural unit (U2) derived from phenylmaleimide or the structural unit (U3) derived from an alkyl acrylate.
[0076] The weight average molecular weight (Mw) of the (meth)acrylic resin is not particularly limited and can be adjusted according to the purpose. The weight average molecular weight of the (meth)acrylic resin is preferably 100,000 or more, more preferably 1,000,000 or more, from the viewpoint of, for example, promoting entanglement between resin molecules to increase the toughness of the base film and make it difficult to break, and from the viewpoint of appropriately increasing the humidity expansion coefficient and making it easy to adjust the curl amount to a level preferable for adhesion. When the weight average molecular weight of the (meth)acrylic resin is 1,000,000 or more, the toughness of the obtained base film can be increased. Thereby, in the manufacturing process, when the base film is transported as a laminated film described later, the breakage of the base film due to the transport tension can be suppressed, and the transport stability can be improved. From the same viewpoint, the weight average molecular weight of the (meth)acrylic resin is more preferably in the range of 1,500,000 to 3,000,000. The method for measuring the weight average molecular weight is as follows.
[0077] <Gel permeation chromatography> Solvent: Methylene chloride Column: Shodex K806, K805, K803G (Showa Denko K.K., three columns connected together) Column temperature: 25℃ Sample concentration: 0.1% by mass Detector: RI Model 504 (GL Sciences) Pump: L6000 (Hitachi, Ltd.) Flow rate: 1.0mL / min Calibration curve: A calibration curve was used using 13 samples of standard polystyrene STK standard polystyrene (manufactured by Tosoh Corporation) in the range of Mw=500 to 2,800,000. It is preferable to use the 13 samples at approximately equal intervals.
[0078] Styrene / (meth)acrylate copolymer Styrene-(meth)acrylate copolymers (hereinafter referred to as styrene-acrylic resins) have excellent transparency when used as base films. In addition, the moisture absorption expansion coefficient can be adjusted by the copolymerization ratio of the styrene portion, so curling of the laminate can be controlled by changing these ratios.
[0079] Styrene-acrylic resins are formed by addition polymerization of at least styrene monomer and (meth)acrylic acid ester monomer. Styrene monomers include styrene, which has the structural formula CH2=CH-C6H5, as well as styrene derivatives that have known side chains or functional groups in the styrene structure.
[0080] In addition, the (meth)acrylic acid ester monomer includes acrylic acid esters and methacrylic acid esters represented by CH(R1)=CHCOOR2 (R1 represents a hydrogen atom or a methyl group, and R2 represents an alkyl group having 1 to 24 carbon atoms), as well as acrylic acid ester derivatives and methacrylic acid ester derivatives having known side chains or functional groups in the structure of these esters.
[0081] Examples of styrene monomers include styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, α-methylstyrene, p-phenylstyrene, p-ethylstyrene, 2,4-dimethylstyrene, p-tert-butylstyrene, pn-hexylstyrene, pn-octylstyrene, pn-nonylstyrene, pn-decylstyrene, and pn-dodecylstyrene.
[0082] Examples of the (meth)acrylic acid ester monomer include acrylic acid ester monomers such as methyl acrylate, ethyl acrylate, isopropyl acrylate, n-butyl acrylate, t-butyl acrylate, isobutyl acrylate, n-octyl acrylate, 2-ethylhexyl acrylate (2EHA), stearyl acrylate, lauryl acrylate, and phenyl acrylate; and methacrylic acid esters such as methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, isopropyl methacrylate, isobutyl methacrylate, t-butyl methacrylate, n-octyl methacrylate, 2-ethylhexyl methacrylate, stearyl methacrylate, lauryl methacrylate, phenyl methacrylate, diethylaminoethyl methacrylate, and dimethylaminoethyl methacrylate.
[0083] In this specification, the term "(meth)acrylic acid ester monomer" is a general term for "acrylic acid ester monomer" and "methacrylic acid ester monomer" and means one or both of them. For example, "methyl (meth)acrylate" means one or both of "methyl acrylate" and "methyl methacrylate".
[0084] The (meth)acrylic acid ester monomer may be one or more kinds. For example, it is possible to form a copolymer using a styrene monomer and two or more kinds of acrylic acid ester monomers, to form a copolymer using a styrene monomer and two or more kinds of methacrylic acid ester monomers, or to form a copolymer using a styrene monomer, an acrylic acid ester monomer, and a methacrylic acid ester monomer in combination.
[0085] The weight average molecular weight (Mw) of the styrene-acrylic resin is preferably in the range of 5,000 to 150,000, and more preferably in the range of 30,000 to 120,000, from the viewpoint of easy control of plasticity.
[0086] The styrene-acrylic resin used in the present invention may be a commercially available product, and an example thereof is MS resin "TX320XL" manufactured by Denka Co., Ltd.
[0087] <Rubber particles> The base film according to the present invention, particularly when a (meth)acrylic resin or a styrene-(meth)acrylate copolymer is used, preferably contains rubber particles in a range of 40 to 85 mass % from the viewpoint of imparting toughness (flexibility) and improving fold mark resistance.
[0088] The rubber particles are particles containing a rubber-like polymer. The rubber-like polymer is a soft crosslinked polymer having a glass transition temperature of 20° C. or less. Examples of such crosslinked polymers include butadiene-based crosslinked polymers, (meth)acrylic crosslinked polymers, and organosiloxane crosslinked polymers. Among them, (meth)acrylic crosslinked polymers are preferred, and acrylic crosslinked polymers (acrylic rubber-like polymers) are more preferred, from the viewpoint of having a small refractive index difference with the (meth)acrylic resin and being less likely to impair the transparency of the base film.
[0089] That is, the rubber particles are preferably particles containing the acrylic rubber-like polymer (a).
[0090] Regarding the acrylic rubber polymer (a): The acrylic rubber-like polymer (a) is a crosslinked polymer containing a structural unit derived from an acrylic acid ester as a main component. "Containing as a main component" means that the content of the structural unit derived from an acrylic acid ester is within the range described below. The acrylic rubber-like polymer (a) is preferably a crosslinked polymer containing a structural unit derived from an acrylic acid ester, a structural unit derived from another monomer copolymerizable therewith, and a structural unit derived from a polyfunctional monomer having two or more radically polymerizable groups (non-conjugated reactive double bonds) in one molecule.
[0091] The acrylic acid ester is preferably an alkyl acrylate ester having an alkyl group having 1 to 12 carbon atoms, such as methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, sec-butyl acrylate, isobutyl acrylate, benzyl acrylate, cyclohexyl acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, etc. The acrylic acid ester may be one type or two or more types.
[0092] The content of structural units derived from acrylic esters is preferably in the range of 40 to 80 mass % relative to all structural units constituting the acrylic rubber-like polymer (a1), and more preferably in the range of 50 to 80 mass %. When the content of acrylic esters is within the above range, sufficient toughness is easily imparted to the protective film.
[0093] The copolymerizable other monomer is a monomer copolymerizable with an acrylic acid ester other than a polyfunctional monomer. That is, the copolymerizable monomer does not have two or more radical polymerizable groups. Examples of the copolymerizable monomer include methacrylic acid esters such as methyl methacrylate; styrenes such as styrene and methylstyrene; (meth)acrylonitriles; (meth)acrylamides; and (meth)acrylic acid. Among them, the copolymerizable other monomer preferably includes styrenes. The copolymerizable other monomer may be one type or two or more types.
[0094] The content of structural units derived from other copolymerizable monomers is preferably in the range of 5 to 55 mass %, more preferably 10 to 45 mass %, based on all structural units constituting the acrylic rubber-like polymer (a).
[0095] Examples of the polyfunctional monomer include allyl (meth)acrylate, triallyl cyanurate, triallyl isocyanurate, diallyl phthalate, diallyl maleate, divinyl adipate, divinyl benzene, ethylene glycol di(meth)acrylate, diethylene glycol (meth)acrylate, triethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, dipropylene glycol di(meth)acrylate, and polyethylene glycol di(meth)acrylate.
[0096] The content of the structural unit derived from the polyfunctional monomer is preferably in the range of 0.05 to 10 mass % and more preferably in the range of 0.1 to 5 mass % based on all structural units constituting the acrylic rubber-like polymer (a). When the content of the polyfunctional monomer is 0.05 mass % or more, the degree of crosslinking of the obtained acrylic rubber-like polymer (a) is easily increased, so that the hardness and rigidity of the obtained base film are not excessively impaired, and when it is 10 mass % or less, the toughness of the base film is not easily impaired.
[0097] The monomer composition constituting the acrylic rubber-like polymer (a) can be measured, for example, by the peak area ratio detected by pyrolysis GC-MS.
[0098] The glass transition temperature (Tg) of the rubbery polymer is preferably 0° C. or lower, and more preferably −10° C. or lower. When the glass transition temperature (Tg) of the rubbery polymer is 0° C. or lower, it is possible to impart appropriate toughness to the film. The glass transition temperature (Tg) of the rubbery polymer is measured by the same method as described above.
[0099] The glass transition temperature (Tg) of the rubbery polymer can be adjusted by the composition of the rubbery polymer. For example, in order to lower the glass transition temperature (Tg) of the acrylic rubbery polymer (a), it is preferable to increase the mass ratio of the acrylic acid ester having an alkyl group with 4 or more carbon atoms to the other copolymerizable monomer in the acrylic rubbery polymer (a) (for example, 3 or more, preferably in the range of 4 to 10).
[0100] The particles containing the acrylic rubber-like polymer (a) may be particles made of the acrylic rubber-like polymer (a), or particles having a hard layer made of a hard crosslinked polymer (c) having a glass transition temperature of 20° C. or higher and a soft layer made of the acrylic rubber-like polymer (a) arranged around the hard layer (these are also called "elastomers"); or particles made of an acrylic graft copolymer obtained by polymerizing a mixture of monomers such as methacrylic acid esters in at least one stage in the presence of the acrylic rubber-like polymer (a). The particles made of the acrylic graft copolymer may be core-shell type particles having a core containing the acrylic rubber-like polymer (a) and a shell covering the core.
[0101] Core-shell type rubber particles containing acrylic rubber-like polymers: (Core) The core part contains an acrylic rubber-like polymer (a) and may further contain a hard crosslinked polymer (c) as necessary. That is, the core part may have a soft layer made of an acrylic rubber-like polymer and a hard layer made of a hard crosslinked polymer (c) disposed inside the soft layer.
[0102] The crosslinked polymer (c) may be a crosslinked polymer mainly composed of a methacrylic acid ester. That is, the crosslinked polymer (c) is preferably a crosslinked polymer containing a structural unit derived from a methacrylic acid alkyl ester, a structural unit derived from another monomer copolymerizable therewith, and a structural unit derived from a polyfunctional monomer.
[0103] The methacrylic acid alkyl ester may be the above-mentioned methacrylic acid alkyl ester; the other copolymerizable monomer may be the above-mentioned styrenes, acrylic acid esters, etc.; and the polyfunctional monomer may be the same as those exemplified as the above-mentioned polyfunctional monomers.
[0104] The content of the structural unit derived from the methacrylic acid alkyl ester may be in the range of 40 to 100% by mass relative to all structural units constituting the crosslinked polymer (c). The content of the structural unit derived from the other copolymerizable monomer may be in the range of 60 to 0% by mass relative to all structural units constituting the other crosslinked polymer (c). The content of the structural unit derived from the polyfunctional monomer may be in the range of 0.01 to 10% by mass relative to all structural units constituting the other crosslinked polymer.
[0105] (Shell part) The shell portion contains a methacrylic polymer (b) (another polymer) that is graft-bonded to the acrylic rubber-like polymer (a) and contains, as a main component, a structural unit derived from a methacrylic acid ester. "Containing as a main component" means that the content of the structural unit derived from a methacrylic acid ester falls within the range described below.
[0106] The methacrylic acid ester constituting the methacrylic polymer (b) is preferably a methacrylic acid alkyl ester, such as methyl methacrylate, in which the alkyl group has a carbon number of 1 to 12. The methacrylic acid ester may be one type or two or more types.
[0107] The content of the methacrylic acid ester is preferably 50% by mass or more based on all structural units constituting the methacrylic polymer (b). When the content of the methacrylic acid ester is 50% by mass or more, compatibility with the methacrylic resin containing a structural unit derived from methyl methacrylate as a main component is easily obtained. From the above viewpoint, the content of the methacrylic acid ester is more preferably 70% by mass or more based on all structural units constituting the methacrylic polymer (b).
[0108] The methacrylic polymer (b) may further contain structural units derived from other monomers copolymerizable with the methacrylic acid ester. Examples of the copolymerizable other monomers include acrylic acid esters such as methyl acrylate, ethyl acrylate, and n-butyl acrylate; and (meth)acrylic monomers having an alicyclic ring, a heterocyclic ring, or an aromatic ring (ring-containing (meth)acrylic monomers) such as benzyl (meth)acrylate, dicyclopentanyl (meth)acrylate, and phenoxyethyl (meth)acrylate.
[0109] The content of structural units derived from copolymerizable monomers is preferably 50% by mass or less, and more preferably 30% by mass or less, based on all structural units constituting the methacrylic polymer (b).
[0110] In the present embodiment, when the base film is not stretched, the shape of the rubber particles may be close to a perfect sphere, that is, the aspect ratio of the rubber particles when the cross section or surface of the base film is observed may be about 1 to 2.
[0111] The average particle size of the rubber particles is preferably in the range of 100 to 400 nm. When the average particle size of the rubber particles is 100 nm or more, sufficient toughness and stress relaxation properties are easily imparted to the base film, and when it is 400 nm or less, the transparency of the base film is less likely to be impaired. From the same viewpoint, the average particle size of the rubber particles is more preferably in the range of 150 to 300 nm.
[0112] The average particle size of the rubber particles can be calculated by the following method.
[0113] The average particle size of rubber particles can be measured as the average of the circle-equivalent diameters of 100 particles obtained by SEM or TEM photography of the surface or slice of the substrate film. The circle-equivalent diameter can be determined by converting the projected area of the particle obtained by photography into the diameter of a circle having the same area. In this case, rubber particles observed by SEM observation and / or TEM observation at a magnification of 5000 times are used to calculate the average particle size.
[0114] The content of the rubber particles is not particularly limited, but is preferably in the range of 40 to 85% by mass, and more preferably in the range of 45 to 75% by mass, based on the base film.
[0115] <Cycloolefin resin> The cycloolefin resin used in the substrate film is preferably a polymer of a cycloolefin monomer, or a copolymer of a cycloolefin monomer and another copolymerizable monomer.
[0116] The cycloolefin monomer is preferably a cycloolefin monomer having a norbornene skeleton, and more preferably a cycloolefin monomer having a structure represented by the following general formula (A-1) or (A-2).
[0117] [ka]
[0118] In general formula (A-1), R 1 ~R 4 each independently represents a hydrogen atom, a hydrocarbon group having 1 to 30 carbon atoms, or a polar group, and p represents an integer of 0 to 2. 1 ~R 4 Not all of these represent hydrogen atoms at the same time, and R 1 and R 2 does not simultaneously represent a hydrogen atom, and R 3 and R 4 does not simultaneously represent a hydrogen atom.
[0119] In general formula (A-1), R 1 ~R 4The hydrocarbon group having 1 to 30 carbon atoms represented by the formula (I) is preferably a hydrocarbon group having 1 to 10 carbon atoms, more preferably a hydrocarbon group having 1 to 5 carbon atoms. The hydrocarbon group having 1 to 30 carbon atoms may further have a linking group containing, for example, a halogen atom, an oxygen atom, a nitrogen atom, a sulfur atom, or a silicon atom. Examples of such linking groups include divalent polar groups such as a carbonyl group, an imino group, an ether bond, a silyl ether bond, and a thioether bond. Examples of the hydrocarbon group having 1 to 30 carbon atoms include a methyl group, an ethyl group, a propyl group, and a butyl group.
[0120] In general formula (A-1), R 1 ~R 4 Examples of the polar group represented by the formula (I) include a carboxy group, a hydroxy group, an alkoxy group, an alkoxycarbonyl group, an aryloxycarbonyl group, an amino group, an amide group, and a cyano group. Among them, a carboxy group, a hydroxy group, an alkoxycarbonyl group, and an aryloxycarbonyl group are preferred, and an alkoxycarbonyl group and an aryloxycarbonyl group are preferred from the viewpoint of ensuring solubility during solution casting.
[0121] In the general formula (A-1), p is preferably 1 or 2 from the viewpoint of improving the heat resistance of the optical film. When p is 1 or 2, the obtained polymer becomes bulky and the glass transition temperature is easily improved. In addition, there is an advantage that the polymer becomes slightly responsive to humidity, making it easier to control the curl balance of the laminate.
[0122] [ka]
[0123] In general formula (A-2), R 5 R represents a hydrogen atom, a hydrocarbon group having 1 to 5 carbon atoms, or an alkylsilyl group having an alkyl group having 1 to 5 carbon atoms. 6represents a carboxy group, a hydroxy group, an alkoxycarbonyl group, an aryloxycarbonyl group, an amino group, an amido group, a cyano group, or a halogen atom (a fluorine atom, a chlorine atom, a bromine atom, or an iodine atom). p represents an integer of 0 to 2.
[0124] R in general formula (A-2) 5 preferably represents a hydrocarbon group having 1 to 5 carbon atoms, and more preferably represents a hydrocarbon group having 1 to 3 carbon atoms.
[0125] R in general formula (A-2) 6 preferably represents a carboxy group, a hydroxy group, an alkoxycarbonyl group or an aryloxycarbonyl group, and more preferably an alkoxycarbonyl group or an aryloxycarbonyl group from the viewpoint of ensuring solubility during solution casting.
[0126] In terms of improving the heat resistance of the optical film, p in general formula (A-2) preferably represents 1 or 2. When p represents 1 or 2, the obtained polymer becomes bulky and the glass transition temperature is likely to be improved.
[0127] Cycloolefin monomers having a structure represented by general formula (A-2) are preferred from the viewpoint of improving solubility in organic solvents. In general, by breaking the symmetry of an organic compound, the crystallinity is reduced, and the solubility in organic solvents is improved. R in general formula (A-2) 5 and R 6 is substituted only on the ring carbon atoms on one side of the axis of symmetry of the molecule, so that the molecular symmetry is low. In other words, a cycloolefin monomer having a structure represented by general formula (A-2) has high solubility and is therefore suitable for producing an optical film by a solution casting method.
[0128] The content ratio of the cycloolefin monomer having the structure represented by general formula (A-2) in the polymer of the cycloolefin monomer can be, for example, 70 mol% or more, preferably 80 mol% or more, more preferably 100 mol% based on the total of all the cycloolefin monomers constituting the cycloolefin resin. If the cycloolefin monomer having the structure represented by general formula (A-2) is contained in a certain amount or more, the orientation of the resin is increased, so that the retardation value is likely to increase.
[0129] Specific examples of cycloolefin monomers having a structure represented by general formula (A-1) are shown in Exemplary Compounds 1 to 14 below, and specific examples of cycloolefin monomers having a structure represented by general formula (A-2) are shown in Exemplary Compounds 15 to 34 below.
[0130] [ka]
[0131] Examples of the copolymerizable monomer copolymerizable with the cycloolefin monomer include a copolymerizable monomer capable of ring-opening copolymerization with the cycloolefin monomer, and a copolymerizable monomer capable of addition copolymerization with the cycloolefin monomer.
[0132] Examples of copolymerizable monomers capable of ring-opening copolymerization include cycloolefins such as cyclobutene, cyclopentene, cycloheptene, cyclooctene, and dicyclopentadiene.
[0133] Examples of copolymerizable monomers capable of addition copolymerization include unsaturated double bond-containing compounds, vinyl cyclic hydrocarbon monomers, and (meth)acrylates. Examples of unsaturated double bond-containing compounds include olefin compounds having 2 to 12 carbon atoms (preferably 2 to 8), examples of which include ethylene, propylene, and butene. Examples of vinyl cyclic hydrocarbon monomers include vinylcyclopentene monomers such as 4-vinylcyclopentene and 2-methyl-4-isopropenylcyclopentene. Examples of (meth)acrylates include alkyl (meth)acrylates having 1 to 20 carbon atoms, such as methyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and cyclohexyl (meth)acrylate.
[0134] The content of the cycloolefin monomer in the copolymer of a cycloolefin monomer and a copolymerizable monomer can be, for example, in the range of 20 to 80 mol %, preferably 30 to 70 mol %, based on the total of all monomers constituting the copolymer.
[0135] As described above, the cycloolefin resin is a polymer obtained by polymerizing or copolymerizing a cycloolefin monomer having a norbornene skeleton, preferably a cycloolefin monomer having a structure represented by general formula (A-1) or (A-2), and examples thereof include the following:
[0136] 1) Ring-opening polymers of cycloolefin monomers 2) Ring-opening copolymers of cycloolefin monomers and copolymerizable monomers capable of ring-opening copolymerization with the cycloolefin monomers. 3) Hydrogenated products of the ring-opening (co)polymers of 1) or 2) above 4) A (co)polymer obtained by cyclizing the ring-opened (co)polymer of 1) or 2) above by the Friedel-Crafts reaction and then hydrogenating the same. 5) Saturated copolymers of cycloolefin monomers and compounds containing unsaturated double bonds 6) Addition copolymers of cycloolefin monomers with vinyl cyclic hydrocarbon monomers and their hydrogenated products 7) Alternating copolymer of cycloolefin monomer and (meth)acrylate
[0137] The polymers 1) to 7) above can be obtained by known methods, for example, the methods described in JP-A-2008-107534 and JP-A-2005-227606. For example, the catalyst and solvent used in the ring-opening copolymerization 2) above can be those described in paragraphs 0019 to 0024 of JP-A-2008-107534. The catalyst used in the hydrogenation 3) and 6) above can be those described in paragraphs 0025 to 0028 of JP-A-2008-107534. The acidic compound used in the Friedel-Crafts reaction 4) above can be those described in paragraph 0029 of JP-A-2008-107534. The catalyst used in the addition polymerization 5) to 7) above can be those described in paragraphs 0058 to 0063 of JP-A-2005-227606. The alternating copolymerization reaction of 7) above can be carried out, for example, by the method described in paragraphs 0071 and 0072 of JP-A No. 2005-227606.
[0138] Among them, the polymers of 1) to 3) and 5) are preferred, and the polymers of 3) and 5) are more preferred. That is, the cycloolefin resin preferably contains at least one of the structural units represented by the following general formula (B-1) and the structural units represented by the following general formula (B-2), and more preferably contains only the structural unit represented by the general formula (B-2), or contains both the structural unit represented by the general formula (B-1) and the structural unit represented by the general formula (B-2). The structural unit represented by the general formula (B-1) is a structural unit derived from the cycloolefin monomer represented by the above-mentioned general formula (A-1), and the structural unit represented by the general formula (B-2) is a structural unit derived from the cycloolefin monomer represented by the above-mentioned general formula (A-2).
[0139] [ka]
[0140] In the general formula (B-1), X represents -CH=CH- or -CH2CH2-. 1 ~R 4 and p are each R in general formula (A-1). 1 ~R 4 and p.
[0141] [ka]
[0142] In the general formula (B-2), X represents -CH=CH- or -CH2CH2-. 5 ~R 6 and p are each R in general formula (A-2). 5 ~R 6 and p.
[0143] The cycloolefin resin used in the present invention may be a commercially available product. Commercially available examples of cycloolefin resins include Arton G (e.g., G7810, etc.), Arton F, Arton R (e.g., R4500, R4900, and R5000, etc.), and Arton RX (e.g., RX4500, etc.) manufactured by JSR Corporation.
[0144] The intrinsic viscosity [η]inh of cycloolefin resin is 0.2 to 5 cm when measured at 30°C. 3 / g, and 0.3 to 3 cm 3 / g, and more preferably in the range of 0.4 to 1.5 cm 3 It is more preferable that the range is / g.
[0145] The number average molecular weight (Mn) of the cycloolefin resin is preferably in the range of 8000 to 100000, more preferably in the range of 10000 to 80000, and even more preferably in the range of 12000 to 50000. The weight average molecular weight (Mw) of the cycloolefin resin is preferably in the range of 20000 to 300000, more preferably in the range of 30000 to 250000, and even more preferably in the range of 40000 to 200000. The number average molecular weight and weight average molecular weight of the cycloolefin resin can be measured in polystyrene equivalent terms by the above-mentioned gel permeation chromatography (GPC).
[0146] When the intrinsic viscosity [η]inh, number average molecular weight and weight average molecular weight are within the above ranges, the cycloolefin resin has good heat resistance, water resistance, chemical resistance, mechanical properties and moldability as a substrate film.
[0147] The glass transition temperature (Tg) of the cycloolefin resin is usually 110° C. or higher, preferably in the range of 110 to 350° C., more preferably in the range of 120 to 250° C., and even more preferably in the range of 120 to 220° C. If the Tg is 110° C. or higher, deformation under high temperature conditions is easily suppressed. On the other hand, if the Tg is 350° C. or lower, molding is easy and deterioration of the resin due to heat during molding is also easily suppressed.
[0148] The content of the cycloolefin resin is preferably 70% by mass or more, and more preferably 80% by mass or more, based on the substrate film.
[0149] <Fine particles> When the substrate film according to the present invention uses a cycloolefin resin, it is also preferable that the substrate film contains fine particles.
[0150] As the fine particles used in the present invention, examples of inorganic compounds include silicon dioxide, titanium dioxide, aluminum oxide, zirconium oxide, calcium carbonate, calcium carbonate, talc, clay, calcined kaolin, calcined calcium silicate, hydrated calcium silicate, aluminum silicate, magnesium silicate, and calcium phosphate.Fine particles of organic compounds can also be preferably used.Examples of organic compounds include polytetrafluoroethylene, cellulose acetate, polystyrene, polymethyl methacrylate, polypropyl methacrylate, polymethyl acrylate, polyethylene carbonate, acrylic styrene resins, silicone resins, polycarbonate resins, benzoguanamine resins, melamine resins, polyolefin powders, polyester resins, polyamide resins, polyimide resins, or polyethylene fluoride resins, and pulverized fractions of organic polymer compounds such as starch, or polymer compounds synthesized by suspension polymerization.
[0151] The fine particles preferably contain silicon because they have a lower turbidity, and silicon dioxide is particularly preferred. For example, Aerosil R972, R972V, R974, R812, 200, 200V, 300, R202, OX50, and TT600 (all manufactured by Nippon Aerosil Co., Ltd.) are commercially available and can be used.
[0152] <Polyimide resin> The polyimide resin may be a polymerization reaction product of a tetracarboxylic dianhydride and a diamine.
[0153] The tetracarboxylic dianhydride may be any of aromatic tetracarboxylic dianhydride, aliphatic tetracarboxylic dianhydride, and alicyclic tetracarboxylic dianhydride, but is preferably aromatic tetracarboxylic dianhydride.The diamine may be any of aromatic diamine, aliphatic diamine, and alicyclic diamine, but is preferably aromatic diamine.
[0154] The weight-average molecular weight Mw of the polyimide resin is not particularly limited, but from the viewpoint of increasing the toughness of the base film and making it less likely to break due to conveying tension, it is preferably in the range of 100,000 to 300,000, and more preferably in the range of 130,000 to 250,000. The method for measuring the weight-average molecular weight Mw of the polyimide resin is the same as described above.
[0155] The content of the polyimide resin is preferably 60% by mass or more, and more preferably 70% by mass or more, based on the base film.
[0156] [1.3] Physical Properties Phase difference Ro and Rt The substrate film according to the present invention can function as an optical film such as a retardation film by being laminated on the surface of a polarizer.
[0157] From the viewpoint of using the substrate film as a retardation film for IPS mode, for example, the in-plane retardation Ro measured at a measurement wavelength of 590 nm under an environment of 23° C. and 55% RH is preferably in the range of 0 to 10 nm, more preferably in the range of 0 to 5 nm, and the thickness direction retardation Rt of the substrate film is preferably in the range of −40 to 40 nm, more preferably in the range of −25 to 25 nm.
[0158] Ro and Rt are defined by the following formulas, respectively.
[0159] Formula (a): Ro = (n x -n y )×d Formula (b): Rt = ((n x +n y ) / 2-n z )×d (In the formula, n x represents the refractive index in the in-plane slow axis direction of the substrate film (the direction in which the refractive index is maximum), n y represents the refractive index in a direction perpendicular to the in-plane slow axis of the substrate film, n z represents the refractive index in the thickness direction of the substrate film, d represents the film thickness (nm) of the substrate film.
[0160] The in-plane slow axis of the substrate film can be confirmed by an automatic birefringence meter Axoscan (Axo Scan Mueller Matrix Polarimeter, manufactured by Axometrics).
[0161] Ro and Rt can be measured by the following method.
[0162] 1) The substrate film is conditioned for 24 hours in an environment of 23°C and 55% RH. The average refractive index of this film is measured with an Abbe refractometer, and the film thickness d is measured with a commercially available micrometer.
[0163] 2) After humidity conditioning, the retardation Ro and Rt of the film at a measurement wavelength of 590 nm are measured in an environment of 23° C. and 55% RH using an automatic birefringence meter Axoscan (Axo Scan Mueller Matrix Polarimeter, manufactured by Axometrics).
[0164] The retardation Ro and Rt of the substrate film can be adjusted by, for example, the type of resin, the stretching conditions, the drying conditions, etc. For example, Rt can be reduced by increasing the drying temperature.
[0165] [1.4] Method for manufacturing base film The form of the base film according to the present invention is not particularly limited, and may be, for example, a strip-like form. That is, the base film according to the present invention is preferably wound into a roll in a direction perpendicular to its width direction to form a roll body.
[0166] [Manufacturing method] The method for producing a base film according to the present invention includes the steps of 1) obtaining a solution for a base film, 2) applying the obtained base film solution to the surface of a support, and 3) removing the solvent from the applied solution for a base film to form a base film.
[0167] 1) A process for obtaining a solution for the base film A solution for a base film (also called a "dope") containing the above-mentioned resin and a solvent is prepared.
[0168] The solvent used in the base film solution is not particularly limited as long as it can disperse or dissolve the resin well. For example, the organic solvent used in the present invention includes alcohols (methanol, ethanol, diol, triol, tetrafluoropropanol, etc.), glycols, cellosolves, ketones (acetone, methyl ethyl ketone, etc.), carboxylic acids (formic acid, acetic acid, etc.), carbonates (ethylene carbonate, propylene carbonate, etc.), esters (ethyl acetate, propyl acetate, etc.), ethers (isopropyl ether, THF, etc.), amides (dimethyl sulfoxide, etc.), hydrocarbons (heptane, etc.), nitriles (acetonitrile, etc.), aromatics (cyclohexylbenzene, toluene, xylene, chlorobenzene, etc.), alkyl halides (dichloromethane (also called "methylene chloride"), etc.), amines (1,4-diazabicyclo[2.2.2]octane, diazabicycloundecene, etc.), lactones, etc.
[0169] Among them, the solvent for the base film is preferably a chlorine-based solvent having a boiling point of 100° C. or less under atmospheric pressure, more specifically, dichloromethane (also called "methylene chloride"), from the viewpoint of ease of handling when preparing a dope for the base film and forming a film. This is preferable from the viewpoint of high solubility and fast drying speed, which allows the film quality of the coating film to be adjusted when preparing a dope for the base film and forming a film. It is also possible to add a hydrophilic solvent. Examples of hydrophilic solvents include ketones and alcohols, and alcohols are preferred. More preferred are isopropanol, ethanol, methanol, etc., and most preferred is methanol. The amount of addition is preferably in the range of 1 to 20% by mass, more preferably in the range of 3 to 10% by mass.
[0170] From the viewpoint of easily adjusting the viscosity to the range described below, the resin concentration of the solution for the base film is preferably in the range of, for example, 1.0 to 20 mass%. Furthermore, from the viewpoint of reducing the amount of shrinkage of the coating film when it is dried, the resin concentration of the solution for the base film is preferably moderately high, more preferably more than 5 mass% to 20 mass% or less, and even more preferably more than 5 mass% to 15 mass% or less. Furthermore, by adjusting the solution concentration, the time until the film is formed is shortened, and the drying time can also be a means of controlling the surface state of the base film. To increase the concentration, a mixed solvent may be used appropriately.
[0171] The viscosity of the solution for the base film is not particularly limited as long as it is sufficient to form a base film with a desired thickness, but is preferably in the range of, for example, 5 to 5000 mPa·s. When the viscosity of the solution for the base film is 5 mPa·s or more, a base film with an appropriate thickness is easily formed, and when it is 5000 mPa·s or less, the occurrence of unevenness in the film thickness due to an increase in the viscosity of the solution can be suppressed. From the same viewpoint, the viscosity of the solution for the base film is more preferably in the range of 100 to 1000 mPa·s. The viscosity of the solution for the base film can be measured at 25°C using an E-type viscometer.
[0172] 2) A process of applying a solution for the base film Next, the obtained solution for the base film is applied to the surface of the support. Specifically, the obtained solution for the base film is coated on the surface of the support. A laminate of the support and the base film is also called a "laminate film."
[0173] <Support> The support is used to support the substrate film during its formation, and usually includes a resin film. The support preferably has a thickness of 50 μm or less. Although the support is thin, it needs to have a certain degree of strength (flexibility and rigidity) as a support, so the support preferably has a thickness of 15 to 45 μm, more preferably 20 to 40 μm.
[0174] Examples of resins that can be used include cellulose ester resins, cycloolefin resins, polypropylene resins, acrylic resins, polyester resins, polyarylate resins, and styrene resins or composite resins thereof. Among these, it is preferable to use polyester resins as they have excellent storage properties in high humidity environments.
[0175] Examples of the resin film include polyester-based resins (e.g., polyethylene terephthalate (PET), polytrimethylene terephthalate (PTT), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), polybutylene naphthalate (PBN), etc.). Among them, from the viewpoint of ease of handling, polyester-based resin films containing polyethylene terephthalate (PET) and polyethylene naphthalate (PEN) are preferred.
[0176] The resin film may be one that has been heat-treated (heat-relaxed) or one that has been stretched.
[0177] The heat treatment is for the purpose of reducing residual stress in the resin film (e.g., residual stress due to stretching), and is not particularly limited, and can be carried out within a range of (Tg+60) to (Tg+180)°C, where Tg is the glass transition temperature of the resin constituting the resin film.
[0178] The stretching treatment is for increasing the residual stress of the resin film, and is preferably performed, for example, in two axial directions of the resin film. The stretching treatment can be performed under any conditions, for example, at a stretching ratio of about 120 to 900%. Whether the resin film is stretched can be confirmed, for example, by whether there is an in-plane slow axis (an axis extending in the direction in which the refractive index is maximum). The stretching treatment may be performed before or after lamination of the base film, but it is preferable to stretch the resin film before lamination.
[0179] The polyester-based resin film (also simply referred to as polyester film) may be a commercially available product, and for example, polyethylene terephthalate film TN100 (manufactured by Toyobo Co., Ltd.) or MELINEX ST504 (manufactured by Teijin DuPont Films Co., Ltd.) may be suitably used.
[0180] The support may further have a release layer provided on the surface of the resin film. The release layer can facilitate peeling of the support from the base film when producing the cover member.
[0181] The release layer may contain a known release agent and is not particularly limited. Examples of the release agent contained in the release layer include silicone-based release agents and non-silicone-based release agents.
[0182] Examples of silicone-based release agents include known silicone-based resins. Examples of non-silicone-based release agents include long-chain alkyl pendant polymers obtained by reacting long-chain alkyl isocyanate with polyvinyl alcohol or ethylene-vinyl alcohol copolymers, olefin resins (e.g., copolymerized polyethylene, cyclic polyolefin, polymethylpentene), polyarylate resins (e.g., polycondensates of aromatic dicarboxylic acid components and dihydric phenol components), fluororesins (e.g., polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyvinyl fluoride (PVF), PFA (copolymer of tetrafluoroethylene and perfluoroalkoxyethylene), FEP (copolymer of tetrafluoroethylene and hexafluoropropylene), ETFE (copolymer of tetrafluoroethylene and ethylene)).
[0183] The thickness of the release layer is not particularly limited as long as it is sufficient to exhibit the desired releasability, but it is preferably in the range of, for example, 0.1 to 1.0 μm.
[0184] The support may contain a plasticizer as an additive. The plasticizer is not particularly limited, but is preferably selected from polyhydric alcohol ester plasticizers, phthalic acid ester plasticizers, citric acid plasticizers, fatty acid ester plasticizers, phosphoric acid ester plasticizers, polycarboxylic acid ester plasticizers, polyester plasticizers, and the like.
[0185] The support may also contain an ultraviolet absorbing agent. Examples of the ultraviolet absorbing agent used include benzotriazole-based, 2-hydroxybenzophenone-based, and salicylic acid phenyl ester-based agents. For example, triazoles such as 2-(5-methyl-2-hydroxyphenyl)benzotriazole, 2-[2-hydroxy-3,5-bis(α,α-dimethylbenzyl)phenyl]-2H-benzotriazole, and 2-(3,5-di-t-butyl-2-hydroxyphenyl)benzotriazole, and benzophenones such as 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-octoxybenzophenone, and 2,2′-dihydroxy-4-methoxybenzophenone can be exemplified.
[0186] Furthermore, the support used in the present invention preferably contains fine particles in order to improve transportability.
[0187] Examples of the fine particles include inorganic compounds such as silicon dioxide, titanium dioxide, aluminum oxide, zirconium oxide, calcium carbonate, calcium carbonate, talc, clay, calcined kaolin, calcined calcium silicate, hydrated calcium silicate, aluminum silicate, magnesium silicate, and calcium phosphate.Fine particles of organic compounds can also be preferably used.Examples of the organic compounds include polytetrafluoroethylene, cellulose acetate, polystyrene, polymethyl methacrylate, polypropyl methacrylate, polymethyl acrylate, polyethylene carbonate, acrylic styrene resins, silicone resins, polycarbonate resins, benzoguanamine resins, melamine resins, polyolefin powders, polyester resins, polyamide resins, polyimide resins, or polyethylene fluoride resins, and pulverized fractions of organic polymer compounds such as starch, or polymer compounds synthesized by suspension polymerization.
[0188] The fine particles preferably contain silicon because they have a lower turbidity, and silicon dioxide is particularly preferred. For example, Aerosil R972, R972V, R974, R812, 200, 200V, 300, R202, OX50, and TT600 (all manufactured by Nippon Aerosil Co., Ltd.) are commercially available and can be used.
[0189] The support used in the present invention can be produced by a conventional production method such as an inflation method, a T-die method, a calendar method, a cutting method, a casting method, an emulsion method, a hot press method, etc., but the film production method is preferably a solution casting method or a melt casting method from the viewpoints of suppressing coloring, suppressing foreign matter defects, suppressing optical defects such as die lines, etc. Furthermore, in the case of the solution casting method, the temperature in the processing step is low, and therefore it is possible to impart high functionality by using various additives.
[0190] In the case of forming a film by the solution casting method, the method of manufacturing the support preferably includes a step of preparing a dope by dissolving and dispersing a thermoplastic resin and additives such as the above-mentioned fine particles in a solvent (dissolving step; dope preparation step), a step of casting the dope onto an endless metal support that moves infinitely (casting step), a step of drying the cast dope as a web (solvent evaporation step), a step of peeling off from the metal support (peeling step), a step of drying, stretching, and width retention (stretching, width retention, drying step), and a step of winding up the finished film into a roll (winding step).
[0191] The support produced as described above is preferably used to form the base film of the present invention by the following method.
[0192] The method for applying the solution for the base film is not particularly limited, and may be a known method such as back-roll coating, gravure coating, spin coating, wire bar coating, roll coating, etc. Among these, the back-coating method is preferred from the viewpoint of forming a coating film that is thin and has a uniform thickness.
[0193] 3) Process for forming the base film Next, the solvent is removed from the base film solution applied to the support to form a base film.
[0194] Specifically, the solution for the base film applied to the support is dried. Drying can be performed, for example, by blowing air or heating. Among them, drying by blowing air is preferable from the viewpoint of easily suppressing curling of the base film, and further, it is preferable to provide a difference in wind speed between the initial stage and the latter stage of drying in terms of controlling the film thickness deviation described below. Specifically, the higher the initial wind speed, the larger the film thickness deviation, and the lower the initial wind speed, the smaller the film thickness deviation tends to be.
[0195] Therefore, by adjusting the drying conditions (for example, drying temperature, drying air volume, drying time, etc.), the density of the base film can be controlled and the film thickness of the base film can be adjusted to satisfy the following formula 1.
[0196] Formula 1: 5<|Average thickness of three randomly selected points in the width direction (B) - average thickness (A)| / average thickness (A)×100<20(%) Here, the average film thickness (A) is the average of the film thickness values at 10 points randomly selected from the film.
[0197] When the value represented by Formula 1 exceeds 5%, the surface has a moderate unevenness, which has the effect of improving adhesion to the upper layer, and when it is less than 20%, the surface unevenness is not too large, so as not to affect the coatability and smoothness of the upper layer.
[0198] The film thickness can be measured using a commercially available film thickness measuring device, for example, F20-UV (manufactured by Filmetrics) as a film thickness measuring system.
[0199] The thickness deviation of the base film is preferably adjusted to within a range of 0.5±0.2 μm. From the viewpoint of improving adhesion to the upper layer, it is preferable to adjust the film quality to be coarser. Specifically, it is preferable to increase the drying speed, and the drying speed is preferably 0.0015 to 0.05 kg / hr m. 2 It is preferable that the maximum flow rate is 0.002 to 0.05 kg / hr m. 2 It is more preferable that the range is .
[0200] The drying rate is expressed as the mass of solvent evaporated per unit time and unit area. The drying rate can usually be adjusted by the drying temperature. The drying temperature depends on the type of solvent used, but can be, for example, in the range of 50 to 200°C ((Tb-50) to (Tb+50)°C, where Tb is the boiling point of the solvent used). Temperature control may be performed in multiple stages. After a certain degree of drying has progressed, the drying rate and film quality can be controlled by drying at a higher temperature.
[0201] As described above, the base film according to the present embodiment may be in a strip shape. Therefore, it is preferable that the method for producing a laminate film according to the present embodiment further includes a step 4) of winding the strip-shaped laminate film into a roll to form a roll body.
[0202] 4) A process of winding up the base film to obtain a roll body. The obtained strip-shaped base film is wound up in a direction perpendicular to its width direction into a roll to form a roll body.
[0203] The length of the strip-shaped base film is not particularly limited, but may be, for example, about 100 to 10,000 m. The width of the strip-shaped laminate film is preferably 1 m or more, more preferably in the range of 1.1 to 4 m. From the viewpoint of improving the uniformity of the film, it is more preferably in the range of 1.3 to 2.5 m.
[0204] [Manufacturing equipment] The method for producing the substrate film used in the present invention can be carried out, for example, by using a production apparatus shown in FIG.
[0205] 3 is a schematic diagram of a manufacturing apparatus B200 for carrying out the method for manufacturing a base film according to the present embodiment. The manufacturing apparatus B200 has a supply section B210, a coating section B220, a drying section B230, a cooling section B240, and a winding section B250. Ba to Bd denote transport rolls that transport the support B110.
[0206] The supply section B210 has a pay-out device (not shown) that pays out a roll B201 of the belt-shaped support B110 wound around a core.
[0207] The coating section B220 is a coating device that includes a backup roll B221 that holds the support B110, a coating head B222 that applies a solution for the base film to the support B110 held by the backup roll B221, and a reduced pressure chamber B223 provided upstream of the coating head B222.
[0208] The flow rate of the base film solution discharged from the coating head B222 can be adjusted by a pump (not shown). The flow rate of the base film solution discharged from the coating head B222 is set to an amount that can stably form a coating layer with a predetermined thickness when continuously coated under the previously adjusted conditions of the coating head B222.
[0209] The decompression chamber B223 is a mechanism for stabilizing a bead (a pool of coating liquid) formed between the substrate film solution from the coating head B222 and the support B110 during coating, and the degree of decompression is adjustable. The decompression chamber B223 is connected to a decompression blower (not shown) so that the inside can be decompressed. The decompression chamber B223 is in a state where there is no air leakage, and the gap with the backup roll is adjusted to be narrow so that a stable bead of coating liquid can be formed.
[0210] The drying section B230 is a drying device that dries the coating film applied to the surface of the support B110, and has a drying chamber B231, an inlet B232 for drying gas, and an outlet B233. The temperature and volume of the drying air are appropriately determined depending on the type of coating film and the type of support B110. By setting conditions such as the temperature and volume of the drying air and the drying time in the drying section B230, the amount of residual solvent in the coating film after drying can be adjusted. The amount of residual solvent in the coating film after drying can be measured by comparing the unit mass of the coating film after drying with the mass of the coating film after it has been thoroughly dried.
[0211] (Residual Solvent Amount) Since the base film is obtained by applying a solution for the base film, the solvent from the solution may remain. The amount of residual solvent can be controlled by the concentration of the solvent and coating solution used, the wind speed used to dry the base film, the drying temperature and time, the conditions of the drying room (outside air or internal air circulation), the heating temperature of the back roll during application, etc.
[0212] As mentioned above, rapid drying makes the film sparse, making it possible to control the surface condition.
[0213] From the viewpoint of curl balance of the base film, it is preferable that the residual solvent amount in the base film satisfies the following formula 2, where the residual solvent amount in the base film is S1.
[0214] formula 2 10 <S1<1000(ppm) Specifically, the residual solvent content of the substrate film is more preferably less than 800 ppm, and more preferably less than 500 to 700 ppm in consideration of the curl balance of the substrate film. In addition, by selecting a solvent / coating process that leaves the solvent on the substrate, the adhesion between the substrate and the substrate film is improved. The residual solvent content of the substrate is preferably in the range of 10 to 100 ppm.
[0215] The amount of residual solvent in the support and the base film can be measured by headspace gas chromatography. In the headspace gas chromatography method, a sample is sealed in a container, heated, and the gas in the container is quickly injected into a gas chromatograph in a state where the container is filled with volatile components, and mass analysis is performed to identify the compounds and quantify the volatile components. In the headspace method, the gas chromatograph makes it possible to observe all peaks of the volatile components, and by using an analysis method utilizing electromagnetic interaction, it is also possible to quantify volatile substances, monomers, etc. with high accuracy.
[0216] The cooling section B240 cools the temperature of the support B110 having the coating film (substrate film) obtained by drying in the drying section B230, and adjusts it to an appropriate temperature. The cooling section B240 has a cooling chamber B241, a cooling air inlet B242, and a cooling air outlet B243. The temperature and volume of the cooling air can be appropriately determined depending on the type of coating film and the type of support B110. Furthermore, if an appropriate cooling temperature can be achieved without providing the cooling section B240, the cooling section B240 may not be necessary.
[0217] The winding section B250 is a winding device (not shown) for winding up the support B110 on which the base film is formed, to obtain a roll body B251.
[0218] [2] Transparent base material Here, "transparent" means that the total light transmittance measured after humidity control in an environment of 23°C and 55% RH is 80% or more, preferably 85% or more, more preferably 90% or more, and particularly preferably 95% or more. The total light transmittance can be measured according to JIS 7573 (Plastics - Determination of total light transmittance and total light reflectance).
[0219] The transparent substrate according to the present invention is a flexible transparent substrate having a thickness of 5 μm or more and less than 50 μm. If the thickness is less than 5 μm, the strength cannot be maintained, and in addition to the high rate of breakage during processing and the rapid deterioration of yield, the durability is poor, such as breakage due to repeated opening and closing of the display. Furthermore, if the thickness is 50 μm or more, the overall thickness of the cover member becomes too thick, resulting in poor flexibility (such as cracking) and weight, so it is necessary to keep the thickness within the above range. A more preferable thickness is 10 μm or more and less than 30 μm.
[0220] Moreover, it is preferable that the elastic modulus of the transparent substrate according to the present invention is within a range of 55 to 80 GPa, and the elastic modulus ratio between the elastic modulus of the transparent substrate and the base film (elastic modulus of transparent substrate / elastic modulus of base film) is at least 30. This is because, in order to provide a cover member that has improved indentation strength and does not leave fold marks by using a transparent substrate having a low elastic modulus due to thinning, it is necessary to use a base film with a lower elastic modulus, that is, by setting the elastic modulus ratio to the transparent substrate (elastic modulus of transparent substrate / elastic modulus of base film) to at least 30, the protective function of the transparent substrate can be further improved.
[0221] <Measurement of elastic modulus> The conditions for measuring the elastic modulus (also referred to as tensile elastic modulus) of the base film and transparent base material are set as follows, and the elastic modulus is determined by linear regression between strains of 0.05 to 0.25%.
[0222] The tensile modulus in the MD direction is measured according to the following method in accordance with JIS K7127 (1999). 1) Cut the substrate film or transparent substrate into a test piece measuring 100 mm (MD) x 10 mm (TD). 2) Using Orientec's Tensilon RTC-1225A, the test piece is pulled in the longitudinal direction (MD) of the test piece at a pulling speed of 50 mm / min with a chuck distance of 50 mm, and the tensile modulus in the MD is measured. The measurement is performed at 23°C and 55% RH.
[0223] [2.1] Glass substrate In view of excellent durability, flatness, and the like, the transparent substrate according to the present invention is preferably a thin glass substrate, and examples thereof include soda-lime glass and silicate glass. Of these, silicate glass is preferable, and specifically, silica glass or borosilicate glass is more preferable.
[0224] The glass constituting the glass substrate is preferably an alkali-free glass that does not substantially contain an alkali component, specifically, a glass having an alkali component content of 1000 ppm or less. The alkali component content in the glass substrate is preferably 500 ppm or less, more preferably 300 ppm or less. A glass substrate containing an alkali component is prone to the phenomenon of soda blowing due to the substitution of cations on the film surface. This is because the density of the film surface layer is likely to decrease, and the glass substrate is likely to be damaged.
[0225] The glass substrate can be formed by a general known method, such as a float method, a down-draw method, an overflow down-draw method, etc. Among them, the overflow down-draw method is preferred because the surface of the glass substrate does not come into contact with a forming member during forming, and the surface of the obtained glass substrate is less likely to be scratched.
[0226] The glass substrate used in the present invention can be obtained by grinding a thick glass, such as borosilicate glass, to a desired thickness, but it is difficult to obtain a glass substrate having a thickness of less than 200 μm by grinding and polishing a thick glass sheet.
[0227] Therefore, in order to obtain a glass substrate having a thickness of 5 μm or more and less than 50 μm according to the present invention, it is preferable to employ a special float method.
[0228] The thinner the glass plate, the more difficult it is to handle and process the ultra-thin glass plate, and the lower the strength of the glass, increasing the probability of breakage. In order to facilitate the handling and processing of thin glass substrates, a method has been proposed in which the thin glass substrate is processed while being temporarily attached to a thicker support substrate (hereinafter also referred to as a "carrier substrate"), and the support substrate is peeled off as a post-processing step to obtain a thin glass substrate.
[0229] For example, according to the aforementioned WO 2017 / 066924, soda-lime glass having a thickness of less than 100 μm can be produced by the following steps.
[0230] (Step 1) A step of forming a first surface of a glass substrate 22 so that the first surface is in contact with a glass carrier substrate having a bonding surface, and attaching a contact film (also called a "contact film") having adhesive properties to a second surface opposite the first surface.
[0231] That is, as shown in FIG. 4 (Step 1), the manufacturing method of the above-mentioned glass substrate includes a step of pouring a material for forming the glass substrate to a desired thickness into a carrier substrate 21 having sufficient strength and a thickness that is easy to process, forming a first surface of the glass substrate 22 so as to be in contact with the carrier substrate 21, and then attaching a contact film 23 to a second surface on the opposite side of the glass substrate 22.
[0232] (Step 2) Next, the glass base material 22 is peeled off from the carrier substrate 21 by the highly adhesive contact film 23 (FIG. 4 (Step 2)). (Step 3) is characterized by including a step of removing the contact film 23 from the second surface of the glass substrate 22 peeled off from the carrier substrate by a weakening treatment (electromagnetic radiation irradiation 24) that weakens the adhesive strength of the contact film (FIG. 4 (Step 3)).
[0233] In other words, the use of the contact film 23 for safely holding the glass substrate 22 can provide a protective function for the glass substrate 22, thereby protecting, for example, the exposed surface of the glass substrate 22 from mechanical damage that may occur thereto, and allowing safe and easy handling.
[0234] The contact film may comprise a hard or soft material depending on the particular requirements, with polyethylene terephthalate (PET), polyethylene (PE) or polyolefin (PO) being preferred materials.
[0235] The contact film is typically adhered to the glass substrate by an adhesive layer of adhesive provided on one side of the substrate, although it is not excluded that the substrate of the contact film itself has adhesive properties.
[0236] The adhesion between the contact film and the second surface of the glass substrate is selected such that sufficient force can be transferred to the glass substrate upon peeling by the peeling device to eliminate the bonding force between the carrier substrate and the glass substrate upon compression.
[0237] The contact film can be provided as a foil or tape, which can be wound, for example, from a roll, or can be provided as a sheet. Preferably, the contact film has a thickness of 50 μm or more, more preferably 80 μm or more, even more preferably 125 μm or more, and particularly preferably 150 μm or more.
[0238] The glass substrate is preferably made from an alkali-containing glass composition as described above. Preferred glass materials are, for example, lithium aluminosilicate glass, soda-lime glass, borosilicate glass, alkali metal aluminosilicate glass, and aluminosilicate glass with low alkali content. Alkali-free compositions are also preferred. Such glasses are preferably made by, for example, the downdraw process, the overflow downdraw process, or the float process described above.
[0239] The carrier substrate preferably has a thickness of at least 100 μm, preferably 300 μm, more preferably 500 μm, and a maximum dimension of at least 3 inches (1 inch is 2.54 cm), preferably 6 inches, more preferably 8 inches, and particularly preferably 12 inches. In particular, the carrier substrate may have a glass substrate first generation size or larger, such as second generation to eighth generation, or even larger, such as a substrate size of 1×1 m to 3×3 m. The carrier substrate may have various shapes, such as rectangular, quadratic or elliptical, or circular.
[0240] The glass substrate is peeled off from the carrier substrate together with the contact film due to the adhesive force of the contact film, and then the contact film is peeled off to obtain a single glass substrate 22 that becomes the transparent substrate 3 shown in FIG.
[0241] In a preferred embodiment, before removing the contact film from the glass substrate, the contact film is subjected to an adhesion weakening treatment to reduce the adhesion between the contact film and the ultra-thin substrate. The weakening treatment is preferably selected so that the adhesion can be reduced to 0.5 N / 25 mm or less. The weakening treatment can be selected to be in a particular wavelength range, such as infrared or ultraviolet light or visible light. The selected electromagnetic radiation can be narrow band or cover a broader band or can be laser radiation, depending on the adhesive material used.
[0242] Preferably, it is selected outside the visible spectrum so that the adhesive strength does not deteriorate under exposure to visible light. There are a variety of adhesive materials commercially available that can be at least partially deactivated by exposure to such electromagnetic radiation, and the preferred selection will depend on the particular requirements.
[0243] Alternatively, if the adhesiveness of the contact film can be reduced by increasing or decreasing the temperature, it may be advantageous to carry out a heat treatment as the weakening treatment.
[0244] The electromagnetic radiation is preferably applied from the outside of the contact film, i.e., from the side not bonded to the glass substrate. Suitable adhesive materials are widely available, for example, under the trade name "NDS4150-20", and the corresponding weakening treatment includes exposure to ultraviolet light at a wavelength of 365 nm.
[0245] A specific example of the production of the glass substrate will be described in the section entitled "Examples." As the glass substrate described above, thin glass manufactured by SCHOTT, Nippon Electric Glass, etc. can be used.
[0246] [2.2] Thermoplastic resin base material The transparent substrate according to the present invention may be a thermoplastic resin film, and the thermoplastic resin may be, but is not limited to, a cellulose ester resin, a cycloolefin resin, a fumaric acid diester resin, a polypropylene resin, a (meth)acrylic resin, a polyester resin, a polyarylate resin, a polyimide resin, and a styrene resin or a composite resin thereof. Among them, a thermoplastic resin film using a polyimide resin is preferably used as the transparent substrate 3 shown in FIG. 1 in terms of optical and physical properties.
[0247] <Polyimide resin> Polyimide resins can be obtained, for example, by synthesizing a polyamic acid (polyimide precursor) from an acid anhydride and a diamine compound, and then imidizing the polyamic acid with heat or a catalyst.
[0248] The acid anhydride used in the synthesis of the polyimide is not particularly limited, and examples thereof include aromatic tetracarboxylic dianhydrides such as biphenyltetracarboxylic dianhydride (BPDA), terphenyltetracarboxylic dianhydride, benzophenonetetracarboxylic dianhydride, pyromellitic anhydride (PMDA), oxydiphthalic dianhydride, diphenylsulfonetetracarboxylic dianhydride, hexafluoroisopropylidenediphthalic dianhydride, and cyclobutanetetracarboxylic dianhydride.
[0249] The diamine compound used in the synthesis of the polyimide is not particularly limited, but examples thereof include aromatic diamines such as p-phenylenediamine (PDA), m-phenylenediamine, 2,4-diaminotoluene, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl ether (ODA), 3,4'-diaminodiphenyl ether, 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 3,7-diamino-dimethyldibenzothiophene-5,5'-dioxide, 4,4'-diaminobenzophenone, 4,4'-bis(4-aminophenyl)sulfide, 4,4'-diaminobenzanilide, and 1,4-bis(4-aminophenoxy)benzene.
[0250] Furthermore, commercially available polyimide varnishes containing a polyimide precursor as a main component, such as U-Varnish S (manufactured by Ube Industries, Ltd.) and Ecrios (manufactured by Mitsui Chemicals, Inc.), can be used.
[0251] In addition, when using ultraviolet-transmitting polyimide depending on the purpose, for example, as a polyimide mainly composed of a commercially available polyimide precursor (polyamic acid), TORMED-S, X (manufactured by IST), Spicceria HR003, GR003 (all manufactured by Somar), FLUPI (manufactured by NTT), Type HM (manufactured by Toyobo Co., Ltd.), Type-C (manufactured by Mitsui Chemicals, Inc.), PI-100 (manufactured by Maruzen Chemical Co., Ltd.), HDN-20D (manufactured by New Japan Chemical Co., Ltd.), CBDA-6FDAC (manufactured by Central Glass Co., Ltd.), Q-VR-X-1655 (manufactured by PI Giken Co., Ltd.), etc. can also be used.
[0252] [3] Manufacturing method of cover member [3.1] Example of cover member configuration On at least one surface of the transparent substrate, the substrate film (substrate film 1) of the present invention is disposed in the configuration shown in Fig. 1A. As described later, when the display device is a display unit having a polarizing plate, it is a preferred embodiment that the substrate film 1 side of the cover member of the present invention is bonded to the polarizing plate via a pressure-sensitive adhesive layer.
[0253] The arrangement of the base film with respect to the transparent substrate is as follows: on the surface (B surface) which is the back surface of one surface (A surface) of the base film, the film density (ρ A ) versus the film density (ρ B ) ratio (ρ A / ρ B It is preferable that the surface A of the substrate film, in which the value of (a) is adjusted to be within the range of 0.80 to 0.95, is the transparent substrate side.
[0254] It is preferable that a base film 2, which will be described later, is disposed on the surface of the transparent base opposite to the base film 1 (FIG. 1B).
[0255] The base film 1 or 2 is attached to the transparent base material 3 via a pressure-sensitive adhesive layer or an adhesive layer.
[0256] FIG. 5 is a schematic diagram showing lamination of a substrate film with a support and a transparent substrate.
[0257] FIG. 5A shows a laminate of the base film 1 formed on the support 5 described above, and the surface of the base film 1 in contact with the support 5 corresponds to side B.
[0258] Next, as shown in FIG. 5B, surface A of the base film 1 is attached to the transparent base material 3 via the pressure-sensitive adhesive layer 4, and then the support 5 is peeled off.
[0259] [3.2] Adhesive layer The pressure-sensitive adhesive layer is preferably a pressure-sensitive adhesive composition containing a base polymer, a prepolymer and / or a crosslinkable monomer, a crosslinking agent and a solvent, which is dried and partially crosslinked, i.e., at least a part of the pressure-sensitive adhesive composition is crosslinked.
[0260] Examples of the pressure-sensitive adhesive composition include an acrylic pressure-sensitive adhesive composition having a (meth)acrylic polymer as a base polymer, a silicone pressure-sensitive adhesive composition having a silicone polymer as a base polymer, and a rubber pressure-sensitive adhesive composition having a rubber as a base polymer. Among them, from the viewpoints of transparency, weather resistance, heat resistance, and processability, an acrylic pressure-sensitive adhesive composition is preferred.
[0261] The (meth)acrylic polymer contained in the acrylic pressure-sensitive adhesive composition may be a copolymer of a (meth)acrylic acid alkyl ester and a functional group-containing monomer crosslinkable with a crosslinking agent.
[0262] The (meth)acrylic acid alkyl ester is preferably an acrylic acid alkyl ester having an alkyl group having 2 to 14 carbon atoms.
[0263] Examples of functional group-containing monomers crosslinkable with the crosslinking agent include amide group-containing monomers, carboxyl group-containing monomers (such as acrylic acid), and hydroxyl group-containing monomers (such as hydroxyethyl acrylate).
[0264] Examples of the crosslinking agent contained in the acrylic adhesive composition include an epoxy crosslinking agent, an isocyanate crosslinking agent, a peroxide crosslinking agent, etc. The content of the crosslinking agent in the adhesive composition can usually be, for example, 0.01 to 10 parts by mass with respect to 100 parts by mass of the base polymer (solid content).
[0265] The pressure-sensitive adhesive composition may further contain various additives, such as a tackifier, a plasticizer, glass fibers, glass beads, metal powder, other fillers, pigments, colorants, fillers, antioxidants, ultraviolet absorbers, and silane coupling agents, as necessary.
[0266] The thickness of the pressure-sensitive adhesive layer is usually about 3 to 100 μm, and preferably in the range of 5 to 50 μm.
[0267] The surface of the pressure-sensitive adhesive layer is protected by a release film that has been subjected to a release treatment. Examples of the release film include plastic films such as acrylic films, polycarbonate films, polyester films, and fluororesin films.
[0268] [3.3] Adhesive layer Instead of the pressure-sensitive adhesive layer, an adhesive layer can be used, and the pressure-sensitive adhesive layer 4 shown in FIG. 1 can be an adhesive layer.
[0269] The adhesive layer is disposed between the substrate film and the transparent substrate. It is also preferable that the adhesive layer is disposed between a polarizing plate described later to constitute a display device. The types of adhesives contained in the adhesive layers may be the same or different.
[0270] The adhesive layer may be a layer obtained from a water-soluble polymer, or may be a layer of a cured product of an active energy ray-curable adhesive. In the case of a water-soluble polymer, the adhesive layer may be formed via, for example, an adhesive made of a vinyl alcohol-based polymer, or an adhesive made of at least a water-soluble crosslinking agent of a vinyl alcohol-based polymer such as boric acid, borax, glutaraldehyde, melamine, or oxalic acid. Such an adhesive layer is formed as a coating and drying layer of an aqueous solution, and when preparing the aqueous solution, other additives and catalysts such as acids may be added as necessary.
[0271] The active energy ray-curable adhesive may be a photoradical polymerizable composition or a photocationically polymerizable composition, of which a photocationically polymerizable composition is preferred.
[0272] The photocationically polymerizable composition contains an epoxy compound and a photocationic polymerization initiator.
[0273] An epoxy compound is a compound having one or more, preferably two or more, epoxy groups in a molecule. Examples of epoxy compounds include hydrogenated epoxy compounds (glycidyl ether of polyol having an alicyclic ring) obtained by reacting epichlorohydrin with an alicyclic polyol; aliphatic epoxy compounds such as polyglycidyl ether of an aliphatic polyhydric alcohol or its alkylene oxide adduct; and alicyclic epoxy compounds having one or more epoxy groups bonded to an alicyclic ring in a molecule. Only one type of epoxy compound may be used, or two or more types may be used in combination.
[0274] The photocationic polymerization initiator may be, for example, an aromatic diazonium salt; an onium salt such as an aromatic iodonium salt or an aromatic sulfonium salt; or an iron-arene complex.
[0275] The photocationic polymerization initiator may further contain additives, such as a cationic polymerization accelerator such as oxetane or polyol, a photosensitizer, an ion trapping agent, an antioxidant, a chain transfer agent, a tackifier, a thermoplastic resin, a filler, a flow control agent, a plasticizer, an antifoaming agent, an antistatic agent, a leveling agent, or a solvent, as necessary.
[0276] The thickness of the adhesive layer is not particularly limited, but is preferably in the range of 0.01 to 10 μm, and more preferably in the range of 0.01 to 5 μm.
[0277] [3.4] Base film 2 The opposing film of the base film 1 may be the base film 1, but another resin film may also be used, examples of which include a cycloolefin resin, a polypropylene resin, an acrylic resin, a polyester resin, a polyarylate resin, a cellulose ester resin, a styrene resin, or a composite resin thereof. Among these, it is preferable to use a resin film containing a polyester resin, which has excellent storage stability in a high humidity environment.
[0278] Examples of the resin film include polyester-based resins (e.g., polyethylene terephthalate (PET), polytrimethylene terephthalate (PTT), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), polybutylene naphthalate (PBN), etc.). Among them, from the viewpoint of ease of handling, polyester-based resin films containing polyethylene terephthalate (PET) and polyethylene naphthalate (PEN) are preferred.
[0279] The resin film may be one that has been heat-treated (heat-relaxed) or one that has been stretched.
[0280] The heat treatment is for the purpose of reducing residual stress in the resin film (e.g., residual stress due to stretching), and is not particularly limited, and can be carried out within a range of (Tg+60) to (Tg+180)°C, where Tg is the glass transition temperature of the resin constituting the resin film.
[0281] The stretching treatment is for increasing the residual stress of the resin film, and is preferably performed, for example, in two axial directions of the resin film. The stretching treatment can be performed under any conditions, for example, at a stretching ratio of about 120 to 900%. Whether the resin film is stretched can be confirmed, for example, by whether there is an in-plane slow axis (an axis extending in the direction in which the refractive index is maximum). The stretching treatment may be performed before or after lamination of the base film, but it is preferable to stretch the resin film before lamination.
[0282] The polyester-based resin film (also simply referred to as polyester film) may be a commercially available product, and for example, polyethylene terephthalate film TN100 (manufactured by Toyobo Co., Ltd.) or MELINEX ST504 (manufactured by Teijin DuPont Films Co., Ltd.) may be suitably used.
[0283] The thickness of the base film 2 can be appropriately determined, but is preferably within the range of 10 to 100 μm from the viewpoint of making the cover member thinner, and more preferably within the range of 10 to 50 μm.
[0284] Furthermore, the base film 2 may be provided with a functional layer such as a hard coat layer.
[0285] (Hard coat layer) The polyester film that is placed on the surface of the foldable display to protect the display preferably has a hard coat layer on its surface. The hard coat layer is preferably placed on the display surface side of the polyester film and used in the display. The resin that forms the hard coat layer can be any resin, including acrylic, siloxane, inorganic hybrid, urethane acrylate, polyester acrylate, and epoxy, without any particular limitation. Two or more types of materials can be mixed and used, and particles such as inorganic filler and organic filler can be added.
[0286] The thickness of the hard coat layer is preferably in the range of 1 to 50 μm. If the thickness is 1 μm or more, the hard coat layer is sufficiently cured and a good pencil hardness is obtained. Furthermore, if the thickness is 50 μm or less, curling due to cure shrinkage of the hard coat layer can be suppressed, and the handling property of the film can be improved.
[0287] The hard coat layer can be applied by any method including, but not limited to, a wire bar, a gravure coater, a die coater, a knife coater, etc., and can be appropriately selected depending on the viscosity and film thickness.
[0288] The hard coat layer can be cured by energy rays such as ultraviolet rays and electron beams, or by heat, and is preferably cured by ultraviolet rays or electron beams in order to reduce damage to the film.
[0289] The pencil hardness of the hard coat layer is preferably B or more, more preferably H or more, and particularly preferably 2H or more. If the hard coat layer has a pencil hardness of B or more, it is not easily scratched and does not reduce visibility. In general, the harder the hard coat layer has, the more preferable the pencil hardness is, but it may be 9H or less, or 8H or less, or even 6H or less can be used without any practical problems.
[0290] The hard coat layer used in the present invention can be used for the purpose of protecting a display by increasing the pencil hardness of the surface as described above, and preferably has a high transmittance. The transmittance of the hard coat film is preferably 87% or more, more preferably 88% or more. If the transmittance is 87% or more, sufficient visibility can be obtained. The total light transmittance of the hard coat film is generally preferably as high as possible, but may be 99% or less, or may be 97% or less. In addition, the haze of the hard coat film is generally preferably low, and is preferably 3% or less. The haze of the hard coat film is more preferably 2% or less, and most preferably 1% or less. If the haze is 3% or less, the visibility of the image can be improved.
[0291] The hard coat layer may further have other functions added thereto. For example, a hard coat layer having the above-mentioned functions such as an antiglare layer having a certain pencil hardness, an antiglare antireflection layer, an antireflection layer, a low reflection layer, and an antistatic layer is preferably used in the present invention.
[0292] [4] Display device The display device of the present invention is characterized by comprising the cover member or the base film for the cover member of the present invention. The display device of the present invention can be obtained, for example, by bonding the cover member of the present invention to the surface of the display device via a pressure-sensitive adhesive layer or an adhesive layer, preferably via a polarizing plate. The display device is a device having a display mechanism, and includes a light-emitting element or a light-emitting device as a light-emitting source. Examples of the display device include a liquid crystal display device, an organic electroluminescence (EL) display device, an inorganic electroluminescence (EL) display device, a touch panel display device, an electron emission display device (field emission display device (FED, etc.), surface field emission display device (SED)), electronic paper (display device using electronic ink or electrophoretic element), a plasma display device, a projection display device (a grating light valve (GLV) display device, a display device having a digital micromirror device (DMD), etc.), and a piezoelectric ceramic display. The liquid crystal display device includes any of a transmissive liquid crystal display device, a semi-transmissive liquid crystal display device, a reflective liquid crystal display device, a direct-view liquid crystal display device, and a projection liquid crystal display device. These display devices may be display devices that display two-dimensional images, or stereoscopic display devices that display three-dimensional images. In particular, the display device of the present invention is preferably an organic EL display device or a touch panel display device, and more preferably an organic EL display device.
[0293] In addition, the foldable display is preferably a structure in which a single continuous display can be folded in half when carried, thereby reducing the size by half and improving portability. At the same time, it is desirable that the foldable display is thin and lightweight. Therefore, the bending radius of the foldable display is preferably 5 mm or less, and more preferably 3 mm or less. If the bending radius is 5 mm or less, it is possible to make the display thin when folded. It can be said that the smaller the bending radius, the better, but it may be 0.1 mm or more, or 0.5 mm or more. Even if it is 1 mm or more, the practicality is sufficiently good compared to conventional displays that do not have a folding structure. Here, the bending radius when folded means the inner radius R of the folded part when the cover member 10 is folded in the above-mentioned FIG. 1C or FIG. 1D.
[0294] FIG. 6 shows an example of application of a cover member to an organic EL display, which is an example of the display device of the present invention.
[0295] A typical organic EL display is configured as a display unit including an organic EL layer 101 including an electrode / electron transport layer / light emitting layer / hole transport layer / transparent electrode, and a polarizing plate 102 including a retardation plate (λ / 4 plate) for improving image quality. In a preferred embodiment of the display device 100 of the present invention, the base film 1 side of the cover member 10 of the present invention is bonded to the polarizing plate 102 via an adhesive layer 4.
[0296] According to the embodiment, the display device of the present invention is a display device that not only improves the handleability of the cover member, but also leaves no fold marks on the base film provided on the cover member, and in particular, as a cover member for a foldable display, it has excellent visibility after repeated folding while maintaining mass productivity, and does not cause image distortion at the folded portion of the display. For example, a mobile terminal device equipped with the foldable display provides beautiful images, is highly functional, and is convenient in terms of portability, etc. EXAMPLES
[0297] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. In the examples, the terms "parts" and "%" are used, but they represent "parts by mass" or "% by mass" unless otherwise specified.
[0298] <Preparation of base film> <Preparation of Base Film 101> (Support) As a support, a polyethylene terephthalate film (PET film): (TN100 manufactured by Toyobo Co., Ltd., with a release layer containing a non-silicone release agent, film thickness 38 μm) was used.
[0299] (Preparation of solution for base film 101) The following components were mixed to obtain a solution for the base film 101.
[0300] Methylene chloride (boiling point 41°C) 800 parts by mass Acrylic 1: MMA / PMI / MADA copolymer (60 / 20 / 20 mass ratio), Mw: 1.5 million, Tg: 137°C (abbreviations are as follows: MMA: methyl methacrylate, PMI: phenylmaleimide, and MADA: adamantyl acrylate) 20 parts by mass Rubber particles R1: 80 parts by mass Dispersant (polyoxyethylene lauryl ether sodium phosphate: molecular weight 332) Add 0.006% by mass to the base film
[0301] (Preparation of Base Film 101) The solution for the base film 101 was applied onto the release layer of the above support using a die by a backcoat method, and then the base film was dried in the drying step described below to form a base film with a thickness of 5 μm, thereby obtaining the base film 101.
[0302] (initial drying) 1st step: 1 min at 40℃ Second step: 70°C for 1 min 3rd step: 100℃ for 1 minute 4th step: 130℃ for 2 minutes (post-drying) 5th step: 110℃ for 15 minutes
[0303] <Preparation of Rubber Particle R1> The rubber particles used were prepared in the following manner.
[0304] The following materials were charged into an 8 L polymerization apparatus equipped with a stirrer.
[0305] Deionized water 180 parts by weight Polyoxyethylene lauryl ether phosphate 0.002 parts by mass Boric acid 0.473 parts by mass Sodium carbonate 0.473 parts by mass Sodium hydroxide 0.008 parts by mass
[0306] After the inside of the polymerization machine was fully replaced with nitrogen gas, the inside temperature was set to 80°C, and 0.021 parts by mass of potassium persulfate was added as a 2% by mass aqueous solution. Next, a mixture of 21 parts by mass of a monomer mixture (c') consisting of 84.6% by mass of methyl methacrylate, 5.9% by mass of butyl acrylate, 7.9% by mass of styrene, 0.5% by mass of allyl methacrylate, and 1.1% by mass of n-octyl mercaptan and 0.07 parts by mass of polyoxyethylene lauryl ether phosphoric acid was added continuously to the above solution over a period of 63 minutes. The polymerization reaction was continued for another 60 minutes to obtain an innermost hard polymer (c).
[0307] Then, 0.021 parts by mass of sodium hydroxide was added as a 2% by mass aqueous solution, and 0.062 parts by mass of potassium persulfate was added as a 2% by mass aqueous solution. Next, a mixed solution of 0.25 parts by mass of polyoxyethylene lauryl ether phosphoric acid and 39 parts by mass of a monomer mixture (a') consisting of 80.0% by mass of butyl acrylate, 18.5% by mass of styrene, and 1.5% by mass of allyl methacrylate was added continuously over 117 minutes. After the addition was completed, 0.012 parts by mass of potassium persulfate was added as a 2% by mass aqueous solution, and the polymerization reaction was continued for 120 minutes to obtain a soft layer (a layer consisting of an acrylic rubber-like polymer (a)). The glass transition temperature (Tg) of the soft layer was -30°C. The glass transition temperature of the soft layer was calculated by averaging the glass transition temperatures of the homopolymers of each monomer constituting the acrylic rubber-like polymer (a) according to the composition ratio.
[0308] Then, 0.04 parts by mass of potassium persulfate was added as a 2% by mass aqueous solution, and 26.1 parts by mass of a monomer mixture (b') consisting of 97.5% by mass of methyl methacrylate and 2.5% by mass of butyl acrylate was continuously added over 78 minutes. The polymerization reaction was continued for another 30 minutes to obtain a polymer (b).
[0309] The obtained polymer (b) was poured into a 3% by mass aqueous solution of sodium sulfate, salted out and coagulated. After repeated dehydration and washing, it was dried to obtain acrylic graft copolymer particles (rubber particles R1) with a three-layer structure. The average particle size of the obtained rubber particles R1 was 200 nm.
[0310] The average particle size of the rubber particles was measured by the following method.
[0311] (Average particle size) The particle size of the rubber particles in the resulting dispersion was measured using a zeta potential / particle size measurement system (ELSZ-2000ZS, manufactured by Otsuka Electronics Co., Ltd.).
[0312] <Preparation of Base Films 102 to 104> Substrate films 102 to 104 were produced in the same manner as in the production of the substrate film 101, except that the content of the rubber particles R1 was changed to 65, 45, and 20 mass %, respectively.
[0313] <Preparation of Base Film 105> (Support) As a support, a polyethylene terephthalate film (PET film): (TN100 manufactured by Toyobo Co., Ltd., with a release layer containing a non-silicone release agent, film thickness 38 μm) was used.
[0314] (Preparation of solution for base film 105) The following components were mixed to obtain a solution for the base film 105.
[0315] Methylene chloride (boiling point 41°C): 860 parts by mass Methanol (boiling point 65°C): 40 parts by mass COP1 (G7810: ARTON G7810 manufactured by JSR Corporation, Mw: 140,000, cycloolefin resin having a carboxylic acid group) 100 parts by mass Antioxidant (Irganox 1076: BASF: molecular weight 531) Add 0.002% by mass of the base film
[0316] (Preparation of Base Film 105) The solution for the base film 105 was applied onto the release layer of the above support using a die by a backcoat method, and then the base film was dried in the drying step described below to form a base film with a thickness of 5 μm, thereby obtaining the base film 105.
[0317] 1st step: 1 min at 40℃ Second step: 70°C for 1 min 3rd step: 100℃ for 1 minute 4th step: 130℃ for 2 minutes
[0318] <Preparation of Base Film 106> (Support) As a support, a polyethylene terephthalate film (PET film): (TN100 manufactured by Toyobo Co., Ltd., with a release layer containing a non-silicone release agent, film thickness 38 μm) was used.
[0319] (Preparation of polyimide powder) Into a four-neck flask equipped with a dry nitrogen gas inlet tube, a condenser, a Dean-Stark condenser filled with toluene, and a stirrer, 5.146 g (20 mmol) of MeO-DABA represented by the following formula was placed, and 20 mL of γ-butyrolactone (GBL) and 10 mL of toluene were added, followed by stirring at room temperature under a nitrogen stream.
[0320] [ka]
[0321] To this was added 4.483g (20mmol) of cis,cis,cis-1,2,4,5-cyclohexanetetracarboxylic dianhydride (H-PMDA) powder, and the mixture was heated and stirred at 80°C for 6 hours. The external temperature was then raised to 190°C, and the water generated during the imidization was azeotropically distilled off together with toluene. After 6 hours of continued heating, refluxing, and stirring, no more water was generated. The mixture was then heated for 7 hours while distilling off the toluene, and after the toluene was distilled off, methanol was added to cause reprecipitation, yielding 6.4g of polyimide powder (72% yield).
[0322] (Preparation of solution for base film 106) The following components were mixed to obtain a solution for the base film 106.
[0323] Methylene chloride (boiling point 41°C) 900 parts by mass Polyimide 1 (the above polyimide powder) 100 parts by mass
[0324] (Preparation of Base Film 106) The solution for the base film 106 was applied onto the release layer of the above support using a die by a backcoat method, and then the base film was dried in the drying step described below to obtain a base film 106 with a thickness of 5 μm.
[0325] (initial drying) 1st step: 1 min at 40℃ Second step: 70°C for 1 min 3rd step: 100℃ for 1 minute 4th step: 130℃ for 2 minutes (post-drying) 5th step: 110℃ for 15 minutes
[0326] <Preparation of Base Films 107 and 108> Substrate films 107 and 108 were prepared in the same manner as in the preparation of substrate film 101, except that the film thickness was changed to 10 μm and 14 μm, respectively.
[0327] <Preparation of Base Film 109> A substrate film 109 was produced in the same manner as in the production of the substrate film 105, except that the solid content concentration of COP1 (G7810) in the dope was adjusted to 20 mass %.
[0328] <Preparation of Base Film 110> A substrate film 110 was prepared in the same manner as in the preparation of the substrate film 105, except that the dope described below in which silica fine particles were added was used.
[0329] (Preparation of microparticle additive solution) Silica fine particles (Aerosil R812: manufactured by Nippon Aerosil Co., Ltd., primary average particle size: 7 nm, apparent specific gravity 50 g / L) 4 parts by mass Dichloromethane 48 parts by mass Ethanol 48 parts by weight The above was mixed and stirred for 50 minutes in a dissolver, then dispersed in a Manton-Gaulin.Furthermore, it was dispersed in an attritor so that the secondary particle size became the specified size.Then, it was filtered with Finemet NF manufactured by Nippon Seisen Co., Ltd. to prepare a fine particle additive liquid.
[0330] (Preparation of solution for base film 110) A dope having the following composition was prepared. First, dichloromethane and ethanol were added to a pressurized dissolution tank. Cycloolefin resin (DOP): G7810 was added to the pressurized dissolution tank containing the mixed solution of dichloromethane and ethanol while stirring. Furthermore, 15 minutes after the start of solvent addition, the fine particle additive liquid prepared above was added, heated to 80°C, and completely dissolved while stirring. At this time, the temperature was raised from room temperature at 5°C / min, dissolved for 30 minutes, and then cooled at 3°C / min. The obtained solution was filtered using Azumi Filter Paper No. 244 manufactured by Azumi Filter Paper Co., Ltd. to prepare a dope.
[0331] (Dope Composition) COP1(G7810) 100 parts by mass Dichloromethane 200 parts by mass Ethanol 10 parts by weight Particulate additive liquid 1 part by mass
[0332] <Preparation of Base Film 111> Substrate film 111 was produced in the same manner as in the production of substrate film 102, except that during the production process, after peeling off the PET film serving as a support, side B was dried, and then a PET film was attached again to side B and rolled up.
[0333] <Preparation of Base Film 112> A substrate film 112 was produced in the same manner as in the production of the substrate film 105, except that the rubber particles R1 were added to the dope so as to make the content thereof 65% by mass.
[0334] <Preparation of Base Film 113> (Support) Kapton film 200H / V (manufactured by Toray DuPont, film thickness 50 μm) was used as a support.
[0335] (Preparation of Base Film 113) 2,2'-ditrifluoromethyl-4,4'-diaminobiphenyl (TFMB, Toray Fine Chemicals) and 4,4'-diaminodiphenyl ether (DPE, Tokyo Chemical Industry Co., Ltd.) were dissolved in dehydrated dimethylacetamide (DMAc, Tokyo Chemical Industry Co., Ltd., boiling point 165°C) in an amount of 90 mol% based on the total amount of diamines, and 10 mol% of the diamines were cooled to 5°C in an ice-water bath. 2-chloroterephthaloyl chloride (CTPC, Nippon Light Metal Co., Ltd.) was added in an amount of 99 mol% based on the total amount of diamines over 30 minutes while keeping the system in an ice-water bath under a nitrogen flow. After the entire amount was added, the mixture was stirred for about 2 hours to polymerize aromatic polyamide (polymer A). To the resulting solution, allyl glycidyl ether (neutralizer E, manufactured by Tokyo Chemical Industry Co., Ltd.) was added as a neutralizer in an amount equivalent to 100 mol % of the amount of hydrogen chloride generated in the above reaction (i.e., the amount of amide groups in the aromatic polyamide), and the mixture was stirred for approximately 1 hour to obtain an aromatic polyamide solution consisting of polymer A (polyamide 1).
[0336] The obtained aromatic polyamide solution was cast in the form of a film on the support using an applicator at room temperature, and dried in a hot air oven at 115° C. for 30 minutes and at 265° C. for 5 minutes to obtain a substrate film 113 made of polymer A (polyamide 1) with a film thickness of 5 μm. Here, a safety oven SPH100 (manufactured by Espec Corporation) was used as the hot air oven, and it was used one hour after the temperature display reached the set temperature with the open / close damper at 50%.
[0337] <Preparation of Base Film 114> (Support) Kapton film 200H / V (manufactured by Toray DuPont, film thickness 50 μm) was used as a support.
[0338] (Preparation of Base Film 114) Into a 300 mL five-neck round-bottom flask equipped with a stainless steel half-moon stirring blade, a nitrogen inlet tube, a Dean-Stark equipped with a cooling tube, a thermometer, and a glass end cap, 9.76 g (0.028 mol) of 9,9-bis(4-aminophenyl)fluorene (manufactured by Taoka Chemical Co., Ltd.), 8.62 g (0.021 mol) of 2,2-bis[4-(4-aminophenoxy)phenyl]propane (manufactured by Wakayama Seika Kogyo Co., Ltd.), 6.72 g (0.021 mol) of 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl (manufactured by Wakayama Seika Kogyo Co., Ltd.), and 46.86 g of γ-butyrolactone (manufactured by Mitsubishi Chemical Corporation) were added as diamine components, and the mixture was stirred at 200 rpm under a nitrogen atmosphere at an internal temperature of 70°C to obtain a solution.
[0339] To this solution, 16.47 g (0.07 mol) of 1,2,4,5-cyclohexanetetracarboxylic dianhydride (manufactured by Mitsubishi Gas Chemical Co., Ltd.) and 11.72 g of γ-butyrolactone (manufactured by Mitsubishi Chemical Co., Ltd.) were added as a tetracarboxylic acid component in one go, and then 3.54 g of triethylamine (manufactured by Kanto Chemical Co., Ltd.) was added as an imidization catalyst, and the reaction system was heated with a mantle heater and the temperature in the reaction system was raised to 190° C. over about 20 minutes. The components distilled off were collected, and the temperature in the reaction system was maintained at 190° C. and refluxed for 5 hours while adjusting the rotation speed according to the increase in viscosity.
[0340] Thereafter, 97.62 g of γ-butyrolactone (manufactured by Mitsubishi Chemical Corporation) was added, and the temperature in the reaction system was cooled to 120° C., and the mixture was further stirred for about 3 hours to be homogenized, thereby obtaining a polyimide 2 solution having a solid content concentration of 20 mass %. The obtained polyimide 2 solution was then applied onto the support by a backcoat method using a die in the same manner as in the preparation of the base film 101, and the base film was then dried in the drying step described below to form a base film having a thickness of 5 μm, thereby obtaining the base film 114.
[0341] (initial drying) 1st step: 10 minutes at 40℃ Second step: 10 min at 70°C 3rd step: 100℃ for 30 minutes 4th step: 130℃ for 30 minutes (post-drying) 5th step: 250℃ for 30 minutes
[0342] <Preparation of Base Film 115> (Support) As a support, a polyethylene terephthalate film (PET film): (TN100 manufactured by Toyobo Co., Ltd., with a release layer containing a non-silicone release agent, film thickness 38 μm) was used.
[0343] (Preparation of solution for base film 115) Methyl ethyl ketone (MEK) 90 parts by weight Rubber particles R1 10 parts by mass The mixture was stirred with a magnetic stirrer to obtain a solution for the base film 115.
[0344] (Preparation of Base Film 115) The solution for the base film 115 was applied onto the release layer of the above support using a die by a backcoat method, and then the base film was dried in the drying step described below to form a base film with a thickness of 5 μm, thereby obtaining the base film 115.
[0345] (initial drying) 1st step: 1 min at 40℃ Second step: 70°C for 1 min 3rd step: 100℃ for 1 minute 4th step: 130℃ for 2 minutes (post-drying) 5th step: 110℃ for 15 minutes
[0346] <Preparation of Base Film 116> A base film 116 was prepared in the same manner as in the preparation of the base film 102, except that the film thickness was adjusted to 25 μm.
[0347] Evaluation The obtained substrate film was subjected to the following evaluations.
[0348] <Stress-strain curve> The substrate film was cut into a size of 100 mm (MD direction: longitudinal direction) x 10 mm (TD direction: transverse direction) to obtain a sample film. This sample film was conditioned for 24 hours in an environment of 23°C and 55% RH, and the sample film after conditioned was pulled in the MD direction with an Orientec Tensilon RTC-1225A chuck with a chuck distance of 50 mm in accordance with JIS K7127:1999 to obtain a stress-strain curve until breakage. The stress-strain curve is expressed as the vertical axis (stress (MPa)) and the horizontal axis (tensile elongation at break (%)). The stress-strain curve was measured at 23°C and 55% RH at a pulling speed of 50 mm / min.
[0349] The slope of the straight line according to the present invention was determined from the stress-strain curve of the base film obtained by the above measurement.
[0350] As shown in FIG. 2, when a tensile test is performed on a substrate film, a breaking point X is obtained after elongation. When a straight line Y is drawn between the breaking point X and the origin (0 point), the slope α of this straight line is defined as "the slope of the straight line connecting the origin and the breaking point in the stress-strain curve of the substrate film" in the present invention.
[0351] <Measurement of density of sides A and B of base film> The density of the surface (side A and side B) of the base film was measured using X-ray reflectivity (XRR). When X-rays are incident on the film surface at a very shallow angle, they are totally reflected, and when the angle of the incident X-rays is equal to or greater than the critical angle of total reflection, the X-rays penetrate into the film and the reflectivity decreases. The reflectivity profile measured by the XRR method can be analyzed using dedicated reflectivity analysis software. In the present invention, when the angle at which the reflectivity starts to decrease is defined as θa, the density at which the fitting error between the measurement result and the calculation result is the smallest in the range of 2θ from 2θa to 2θa+0.1° is defined as the surface density. At that time, the fitting was performed with the surface roughness in the range of 0 to 1 nm.
[0352] The substrate film was cut into a size of 30 mm x 30 mm, fixed to a sample stage, and measured under the following measurement conditions. (Measurement conditions) Equipment: Thin film X-ray diffraction equipment (Rigaku ATX-G) Sample size: 30mm x 30mm ·Incoming X-ray wavelength: 1.5405Å Measurement range (θ): 0~6° Analysis software: Reflectance analysis software GXRR (Rigaku Corporation)
[0353] <Measurement of elastic modulus of base film> The conditions for measuring the elastic modulus (also called the tensile elastic modulus) were set as follows, and the elastic modulus was determined by linear regression between strains of 0.05 and 0.25%.
[0354] The tensile modulus in the MD direction was measured according to the following method in accordance with JIS K7127 (1999). 1) The substrate film was cut into a test piece measuring 100 mm (MD) x 10 mm (TD). 2) The test piece was pulled in the longitudinal direction (MD) of the test piece at a pulling speed of 50 mm / min using an Orientec Tensilon RTC-1225A with a chuck distance of 50 mm, and the tensile modulus in the MD direction was measured. The measurement was carried out at 23°C and 55% RH. The modulus of elasticity of the transparent substrate described later was also measured in the same manner.
[0355] <Indentation strength> The A and B sides of the base film were measured according to the indentation test procedure specified in ISO 14577. The measurements were performed in an environment of 23°C and 55% RH using an ultra-microhardness tester (manufactured by Fisher Instruments, product name "Fisherscope 100C") as the testing machine and a pyramidal diamond indenter with a square base and a facing angle of 136° as the indenter.
[0356] The measurement was performed by pressing an indenter into the substrate film at a constant speed and applying a load of 10 mN. The Martens hardness was calculated by applying a load (10 mN) to the film and dividing the load by the surface area of the indenter that penetrated beyond the zero contact point.
[0357] Regarding the indentation strength of the base film of the present invention, the Martens hardness was measured according to the above-mentioned method, and the rank of the surface hardness (Martens hardness) was determined for the average value of sides A and B according to the following criteria.
[0358] ◎: Martens hardness is 200N / mm 2 End ○: Martens hardness is 50N / mm 2 More than 200N / mm 2 less than △: Martens hardness is 25N / mm 2 More than 50N / mm 2 less than ×: Martens hardness is 25N / mm 2 less than When the Martens hardness is evaluated as △ or higher, the indentation strength of the base film is improved, and when the base film is provided on a cover member, cracking of the transparent base material is prevented and the handleability of the cover member is improved.
[0359] The configuration of the base film and the evaluation results are shown in Table I below.
[0360] [Table 1]
[0361] <Preparation of transparent substrate 1: In the table, indicated as glass.> A glass substrate having a size of 12 inches was prepared according to the following steps (see FIG. 4).
[0362] (Step 1) A step of forming a first surface of a glass substrate so that it is in contact with a glass carrier substrate having a bonding surface, and attaching a contact film (also called a "contact film") having adhesive properties to a second surface opposite the first surface.
[0363] (Step 2) Next, the glass substrate is peeled off from the carrier substrate by the highly adhesive contact film. (Step 3) A step of removing the contact film from the second surface of the glass substrate peeled off from the carrier substrate by a weakening treatment (electromagnetic radiation exposure) that weakens the adhesive strength of the contact film.
[0364] In step 1, a glass substrate 1 was formed to a predetermined thickness so as to contact a carrier substrate having a thickness of 500 μm, and then the contact film described below was attached. Next, the glass substrate was peeled off together with the contact film from the carrier substrate in 30 seconds to remove the carrier substrate (step 2). The contact film used was a commercially available product named "NDS4150-20" that contains polyolefin (PO) as a substrate having a thickness of 150 μm and a 10 μm adhesive layer.
[0365] Next, the exposed contact film was weakened to reduce its adhesive strength. The weakening treatment involved irradiating the contact film with 365 nm ultraviolet light for 10 seconds. The ultraviolet light irradiation power was approximately 500 mW / cm. 2 The total irradiation energy is 500 mJ / cm2 The adhesive strength before the weakening treatment was about 11 N / 25 mm, and after the weakening treatment, the adhesive strength was reduced to 0.4 N / 25 mm. This made it possible to easily peel the contact film from the glass substrate, and a single glass substrate with a thickness of 28 μm was obtained (step 3).
[0366] The thicknesses of the transparent substrates were adjusted to 8 μm, 28 μm, 45 μm and 54 μm, and the elastic moduli measured by the above-mentioned method were as shown in Table II.
[0367] <Preparation of transparent substrate 2: In the table, indicated as polyimide.> In the preparation of the substrate film 114, the obtained polyimide 2 solution was applied onto a glass plate and held on a hot plate at 100°C for 60 minutes to volatilize the solvent, thereby obtaining a colorless and transparent primary dried film having self-supporting properties. This film was fixed onto a stainless steel frame and heated in a hot air dryer at 250°C for 2 hours to evaporate the solvent, obtaining a transparent substrate 2 having a thickness of 28 μm. The elastic modulus measured by the above-mentioned measurement method was 10 GPa.
[0368] <Preparation of Base Film 2> (Preparation of polyethylene terephthalate pellets (a)) A continuous esterification reaction apparatus consisting of a three-stage complete mixing tank equipped with an agitator, a partial condenser, a raw material inlet, and a product outlet was used as the esterification reaction apparatus. Terephthalic acid (TPA) was supplied at 2 tons / hr, ethylene glycol (EG) was supplied at 2 moles per mole of TPA, and antimony trioxide was supplied in an amount such that the antimony (Sb) atom would be 160 ppm relative to the PET produced. These slurries were continuously supplied to the first esterification reaction vessel of the esterification reaction apparatus and reacted at normal pressure for an average residence time of 4 hours at 255°C.
[0369] Next, the reaction product in the first esterification reactor was continuously taken out of the system and fed to a second esterification reactor, EG distilled from the first esterification reactor was fed into the second esterification reactor in an amount of 8% by mass relative to the produced polymer (produced PET), and an EG solution containing magnesium acetate in an amount such that the magnesium (Mg) atom would be 65 ppm relative to the produced PET and an EG solution containing tetramethylphthalic acid (TMPA) in an amount such that the P atom would be 20 ppm relative to the produced PET were added, and reacted at normal pressure for an average residence time of 1.5 hours at 260° C. Next, the reaction product in the second esterification reactor was continuously taken out of the system and fed to a third esterification reactor, and an EG solution containing TMPA in an amount such that the P atom would be 20 ppm relative to the produced PET was added, and reacted at normal pressure for an average residence time of 0.5 hours at 260° C. The esterification reaction product produced in the third esterification reactor was continuously supplied to a three-stage continuous polycondensation reactor to carry out polycondensation, and was then filtered through a stainless steel sintered filter medium (nominal filtration accuracy: 90% cut of 5 μm particles) to obtain polyethylene terephthalate pellets (a) with an intrinsic viscosity of 0.580 dl / g.
[0370] (Preparation of polyethylene terephthalate film) Pellets of polyethylene terephthalate (a) were fed to an extruder and melted at 285°C. The polymer was filtered through a stainless steel sintered filter medium (nominal filtration accuracy 10μm particles 95% cut), extruded from a die in the form of a sheet, and then contacted with a casting drum with a surface temperature of 30°C using an electrostatic casting method to cool and solidify, producing an unstretched film. The unstretched film was uniformly heated to 75°C using a heating roll, heated to 100°C using a non-contact heater, and roll-stretched (longitudinal stretching) 1.5 times. The obtained uniaxially stretched film was introduced into a tenter, heated to 125°C, stretched laterally 5.5 times, fixed in width, heat-treated at 190°C for 5 seconds, and further relaxed in the width direction by 4% at 100°C to obtain a base film 2, which is a polyethylene terephthalate film with a thickness of 50μm (represented as PET in the table).
[0371] <Preparation of cover member> <Production of Cover Member 201> The base film 101 prepared in Example 1, the transparent base material 1 prepared above, and the base film 2 were bonded together via the following pressure-sensitive adhesive layer to prepare a cover member 201 shown in Table II.
[0372] <Adhesive layer material> (Preparation of Acrylic Polymer) A monomer mixture containing 100 parts of n-butyl acrylate and 5 parts of acrylic acid was charged into a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a cooler. Furthermore, 0.1 parts of 2,2'-azobisisobutyronitrile as a polymerization initiator was charged together with 100 parts of ethyl acetate for 100 parts of the monomer mixture (solid content), and nitrogen gas was introduced while gently stirring to replace the atmosphere with nitrogen. The liquid temperature in the flask was kept at about 55°C, and a polymerization reaction was carried out for 8 hours to prepare a solution of an acrylic polymer with a weight average molecular weight (Mw) of 1.6 million.
[0373] (Preparation of Pressure-Sensitive Adhesive Composition Solution) 0.45 parts of an isocyanate crosslinking agent (Coronate L, trimethylolpropane tolylene diisocyanate, manufactured by Tosoh Corporation) was mixed with 100 parts of the solid content of the acrylic polymer solution obtained above to prepare a solution of an acrylic pressure-sensitive adhesive composition.
[0374] (Formation of adhesive layer and preparation of cover member) Next, the A-side of the base film 101 was subjected to a corona discharge treatment with a corona output intensity of 2.0 kW and a line speed of 18 m / min. The corona discharge-treated surface was coated with the above-prepared adhesive composition solution using a bar coater so that the film thickness after drying would be approximately 3 μm. The film was then dried at 50°C, 60°C, and 70°C in that order for 60 seconds each to form an adhesive layer. After lamination, the support of the base film 101 was peeled off to obtain a cover member 201 (see Figure 5B).
[0375] <Production of cover members 202 to 222> Cover members 202 to 222 were produced in the same manner as in the production of cover member 201, except that the combinations of the types of base film 1, transparent base material, and base film 2 were changed as shown in Table II.
[0376] In the production of the cover member 202, the cover member 214 used the base film 102 produced above as the base film 2. The base film 2 was also bonded such that the surface A of the base film 102 was disposed on the glass base material side. In the production of the cover member 202, the cover member 215 did not have anything bonded to the base film 2 side.
[0377] Evaluation <Folding evaluation> A cover member sample measuring 20 mm in the TD direction and 110 mm in the MD direction is prepared. Using a no-load U-shaped stretch tester (Yuasa System Co., Ltd., DLDMLH-FS), the bending radius is set to 1 mm, and the sample is bent 100 times at a speed of 1 time / second. At that time, the sample is fixed at a position 10 mm from both ends on the MD side, and the bending portion is 20 mm x 90 mm. After the bending process is completed, the sample is placed on a flat surface with the inside of the bend facing down, and the bent portion is measured with a commercially available haze meter to determine the haze value before evaluation as A and the haze value after evaluation as B. The difference between the values (BA) is calculated and the following ranking is performed.
[0378] ◎: Less than 0.2 ○: 0.2 or more and less than 0.5 △: 0.5 or more and less than 1.0 ×: 1.1 or higher △ or above is desirable.
[0379] The configuration of the cover member and the above evaluation results are shown in Table II below.
[0380] [Table 2]
[0381] From the results of Tables I and II, the cover members 201-217 using the base films 101-112 of the present invention obtained superior results in both the indentation strength of the base film and the folding marks of the cover members compared to the cover members 218-221 using the base films 113-116 of the comparative examples and the cover member 222 having a thick transparent base material.
[0382] In addition to improving handleability, the cover member of the present invention has the characteristic that when repeatedly bent, no fold marks are left on the base film provided on the cover member. Therefore, no image distortion occurs at the folded portion of the display, and the cover member-equipped display device has excellent visibility and can be suitably used in foldable displays using organic electroluminescence elements. [Explanation of symbols]
[0383] 1 Base film 1 2 Base film 2 3 Transparent base material 4 Adhesive layer 5 Support 10 Cover member 21 Carrier Board 22 Glass substrate 23 Contact Film 24 Electromagnetic Radiation 100 display device 101 Organic EL layer 102 Polarizing plate B110 Support B120 Base film B200 manufacturing equipment B210 Supply section B220 Application unit B230 Drying section B240 Cooling section B250 Winding section R bending radius
Claims
1. A cover member for a foldable flexible display having a base film and a transparent base material, The thickness of the base film is in the range of 1 μm or more and less than 15 μm, The thickness of the transparent substrate is in the range of 5 μm or more and less than 50 μm, the substrate film contains a cellulose ester-based resin, a cycloolefin-based resin, a fumaric acid diester-based resin, a polypropylene-based resin, a (meth)acrylic resin, a polyester-based resin, a polyarylate-based resin, a polyimide-based resin, a styrene-based resin, or a composite resin thereof; When the relationship between tensile stress and tensile elongation at break of the base film is measured under conditions of 23° C., 55% RH, and a pulling speed of 50 mm / min, the slope of a straight line connecting the origin and the breaking point in a stress-strain curve with stress (MPa) on the vertical axis and tensile elongation (%) on the horizontal axis is within a range of 1.1 MPa / % or more and 25.0 MPa / % or less. A cover member for a foldable flexible display.
2. When the surface of the base film that is attached to the transparent base material is designated as surface A and the back surface of the base film opposite surface A is designated as surface B, The film density (ρ A ) is the film density (ρ B 2. The cover member of a foldable flexible display according to claim 1, wherein the cover member is smaller than the width W of the foldable flexible display.
3. When the surface of the base film that is attached to the transparent base material is surface A and the back surface of the base film opposite surface A is surface B, The film density (ρ A ) to the film density (ρ B ) ratio (ρ A / ρ B 3. The cover member of a foldable flexible display according to claim 1 or 2, characterized in that the value of (a) is within a range of 0.80 to 0.
95.
4. The cover member for a foldable flexible display according to claim 1 or 2, characterized in that the base film contains rubber particles in a range of 40 to 85 mass %.
5. A cover member for a foldable flexible display as described in claim 1 or claim 2, characterized in that the elastic modulus of the transparent substrate is within the range of 55 to 80 GPa, and the ratio of the elastic modulus of the transparent substrate to the elastic modulus of the substrate film (elastic modulus of transparent substrate / elastic modulus of substrate film) is 30 or more.
6. A cover member for a foldable flexible display as described in claim 1 or claim 2, characterized in that the base film contains at least a polyimide-based resin.
7. A cover member for a foldable flexible display as described in claim 1 or claim 2, characterized in that the base film does not contain rubber particles.
8. The thickness of the base film is in the range of 1 μm or more and less than 15 μm, the substrate film contains a cellulose ester-based resin, a cycloolefin-based resin, a fumaric acid diester-based resin, a polypropylene-based resin, a (meth)acrylic resin, a polyester-based resin, a polyarylate-based resin, a polyimide-based resin, a styrene-based resin, or a composite resin thereof; When the relationship between tensile stress and tensile elongation at break of the base film is measured under conditions of 23° C., 55% RH, and a pulling speed of 50 mm / min, the slope of a straight line connecting the origin and the breaking point in a stress-strain curve with stress (MPa) on the vertical axis and tensile elongation (%) on the horizontal axis is within a range of 1.1 MPa / % or more and 25.0 MPa / % or less. A substrate film for a cover member of a foldable flexible display, comprising:
9. The substrate film is attached to a transparent substrate, When the surface of the base film that is attached to the transparent base material is surface A and the back surface of the base film opposite surface A is surface B, The film density (ρ A ) is the film density (ρ B 9. The substrate film for a cover member of a foldable flexible display according to claim 8, characterized in that the substrate film for a cover member of a foldable flexible display has a thickness smaller than 1 / 2 mm.
10. The substrate film is attached to a transparent substrate, When the surface of the base film that is attached to the transparent base material is surface A and the back surface of the base film opposite surface A is surface B, The film density (ρ A ) to the film density (ρ B ) ratio (ρ A / ρ B The substrate film for a cover member of a foldable flexible display according to claim 8 or 9, characterized in that the value of (a) is within a range of 0.80 to 0.
95.
11. The substrate film for a cover member of a foldable flexible display according to claim 8 or claim 9, characterized in that the substrate film contains rubber particles in a range of 40 to 85 mass%.
12. A display device comprising: a cover member for a foldable flexible display according to claim 1 or 2; or a base film for a cover member for a foldable flexible display according to claim 8 or 9.
Citation Information
Patent Citations
Polymer coated thin glass film substrate
JP2002534305A
Hard coating film and image display unit including the same
JP2018045234A
Member for display
JP2018092127A
Polarizing plate and display device
JP2020126226A
Flexible laminate and picture display unit equipped with the same
JP2020135636A